Fluorene derivative, light-emitting element, light-emitting device, electronic device, and lighting device
By using the fluorene derivative represented by the general formula (G1) as the hole transport layer material in the EL layer of the light emitting element, the problems of low luminescence efficiency and high power consumption in the prior art are solved, and high efficiency and low power luminescence is achieved Effect.
Patent Information
- Application Number
- CN202411566970.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2009-05-29
- Filing Date
- 2010-05-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2030-05-19
AI Technical Summary
The existing light emitting elements have low luminous efficiency when high concentrations of organic molecules, and have high power consumption and driving voltage.
The fluorene derivative represented by the general formula (G1) is used as the hole transport layer material, and by applying it to the EL layer of the light emitting element, hole transportability and luminous efficiency are improved, and power consumption and driving voltage are reduced.
The light emitting element with high luminous efficiency has low power consumption and low driving voltage, and is suitable for light emitting devices, electronic devices and lighting devices.
Smart Images

Figure CN119431157A_ABST
Abstract
Description
[0001] This application is a divisional application of the PCT patent application with international application number PCT / JP2010 / 058854 filed on May 19, 2010, application number 201080025006.4 entering the Chinese national phase, and invention name "Fluorene derivatives, light-emitting elements, light-emitting devices, electronic devices and lighting devices", which claims priority on May 29, 2009. Technical Field
[0002] The invention relates to a fluorene derivative, a light-emitting element, a light-emitting device, an electronic device and a lighting device. Background Art
[0003] In recent years, luminescent elements that utilize electroluminescence have been extensively studied and developed. In the basic structure of such luminescent elements, a layer containing a substance having luminescent properties is inserted between a pair of electrodes. By applying a voltage to the element, light emission can be obtained from the substance having luminescent properties.
[0004] Since this type of light-emitting element is of the self-luminous type, it is considered that the light-emitting element has advantages over liquid crystal displays in that pixel visibility is high and backlight is not required, etc., and is therefore suitable for use as a flat panel display element. In addition, this light-emitting element has the advantage that it can be formed into a thin and light element and has an extremely fast response speed.
[0005] Moreover, since such a light-emitting element can be formed into a film shape, planar light emission can be easily obtained. Therefore, a large-area element utilizing planar light emission can be formed. This is a characteristic that is difficult to obtain with a point light source represented by an incandescent lamp and an LED or a line light source represented by a fluorescent lamp. Therefore, the light-emitting element is particularly effective as a surface light source in applications such as lighting.
[0006] Light-emitting elements utilizing electroluminescent properties can be broadly classified according to whether they utilize organic compounds or inorganic compounds as luminescent substances. When an organic compound is used as a luminescent substance, electrons and holes can be injected from a pair of electrodes into a layer containing a light-emitting organic compound by applying a voltage to the light-emitting element, thereby generating a current. Light is emitted when the carriers (electrons and holes) recombine and the electrons and holes of the organic compound return from an excited state to a ground state, wherein the electrons and holes are simultaneously generated in an organic molecule having a luminescent property.
[0007] According to this mechanism, this light-emitting element is called a current excitation type light-emitting element. It should be noted that the excited state generated by the organic compound can be a singlet excited state or a triplet excited state. The light emitted from the singlet excited state is called fluorescence, and the light emitted from the triplet excited state is called phosphorescence.
[0008] In addition to the above-mentioned luminescence by recombination of current-excited carriers, there is also a method of transferring excitation energy to another organic compound, thereby exciting the organic compound to provide light emission. In this element structure, the luminescent material is diffused (doped) into the luminescent layer of an ordinary organic EL. The main material refers to the material into which the luminescent material is diffused, and the dopant refers to the material diffused into the main material. In order to solve the problem of low luminous efficiency of light emission due to the occurrence of stacking interactions when the concentration of organic molecules in organic molecules is high (concentration quenching), it is beneficial to obtain high luminous efficiency by doping organic molecules into the main material and inhibiting stacking. At the same time, the excitation energy of current excitation is transferred from the main material excited by the current to the dopant, so that the dopant emits light.
[0009] This excitation energy transfer occurs only when high excitation energy is transferred to low excitation energy. Therefore, it is preferable to use a material having a high excited state as a host material.
[0010] The organic EL layer has multiple layers, and the carrier transport layer is usually arranged between the light-emitting layer and the electrode. One of the reasons is that the carrier transport layer can prevent the excitation energy in the light-emitting layer from being quenched due to energy transfer to the electrode. In addition, a material (exciton blocking material) with higher excitation energy than the light-emitting layer is preferably used for the carrier transport layer adjacent to the light-emitting layer, so that the excitation energy in the light-emitting layer is not transferred.
[0011] Another reason for providing a carrier injection layer and a carrier transport layer between the light emitting layer and the electrode of the organic EL is to adjust the carrier injection partition between adjacent layers. Accordingly, recombination can be effectively performed in the light emitting layer.
[0012] In the process of improving the element characteristics of such a light-emitting element, there are many problems depending on the material, and in order to solve these problems, improvements have been made in element structure, material development, etc. (for example, see Patent Document 1).
[0013] [References]
[0014] [Patent Document]
[0015] [Patent Document 1] PCT International Publication No. 08 / 062636 Summary of the invention
[0016] An object of one embodiment of the present invention is to provide a novel fluorene derivative as a substance having high hole transport properties. Another object is to provide a light-emitting element having high luminous efficiency by applying the novel fluorene derivative to the light-emitting element. Another object of one embodiment of the present invention is to provide a light-emitting device, an electronic device, and a lighting device each having low power consumption and low driving voltage.
[0017] One embodiment of the present invention is a fluorene derivative represented by the following general formula (G1):
[0018] [Chemical formula 1]
[0019]
[0020] In the formula, R 1 -R 8 independently represent any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted biphenyl group. 1 -α 4 independently represent any substituted or unsubstituted arylene group having 6 to 12 carbon atoms. 1 and Ar 2 independently represents any aromatic group having 6 to 13 ring carbon atoms, Ar 3 represents an alkyl group having 1 to 6 carbon atoms or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms. J, k, m, and n independently represent 0 or 1. It should be noted that at least one of J and k is 1.
[0021] In the above structure, R in the general formula (G1) 1 -R 8 Each independently represents any one of Structural Formula (R-1) to Structural Formula (R-9).
[0022] [Chemical formula 2]
[0023]
[0024] In the above structure, α in the general formula (G1) 1 -α 4 Independently represents any one of Structural Formula (α-1) to Structural Formula (α-3).
[0025] [Chemical formula 3]
[0026]
[0027] In the above structure, Ar in the general formula (G1) 1 and Ar 2 independently represents any one of the structural formulas (Ar-1) to (Ar-6), Ar 3 Represents any one of structural formulas (Ar3-1) to (Ar3-8).
[0028] [Chemical formula 4]
[0029]
[0030] [Chemical formula 5]
[0031]
[0032] Another embodiment of the present invention is represented by the following structural formula (101), structural formula (151) or structural formula (118).
[0033] [Chemical formula 6]
[0034]
[0035] [Chemical formula 7]
[0036]
[0037] [Chemical formula 8]
[0038]
[0039] Another embodiment of the present invention is a light-emitting element including an EL layer between a pair of electrodes, wherein the EL layer includes at least a light-emitting layer and a hole transport layer, and the hole transport layer includes one or more of the above-mentioned fluorene derivatives.
[0040] In addition, another embodiment of the present invention is a light emitting device formed using the above light emitting element. Another embodiment of the present invention is an electronic device formed using the above light emitting device. Another embodiment of the present invention is a lighting device formed using the above light emitting device.
[0041] The light-emitting device of one embodiment of the present invention is a light-emitting device including the aforementioned light-emitting element and a control device, wherein the control device controls the light emission in the light-emitting element. It should be noted that the light-emitting device described in this specification includes an image display device, a light-emitting device or a light source (including a lighting device). In addition, the light-emitting device includes any of the following modules: a module in which a connector (such as a flexible printed circuit (FPC), a tape automated bonding (TAB) tape or a tape carrier package (TCP)) is connected to a board; a module in which a printed wiring board is assembled at the end of a TAB tape or a TCP; an integrated circuit (IC) module directly mounted on a light-emitting element by a chip on glass (Chip on Glass (COG)) method.
[0042] Furthermore, an electronic device used in a display portion in one embodiment of the light emitting device of the present invention is also included in the scope of the present invention. Therefore, an embodiment of the electronic device of the present invention includes a display portion, wherein the display portion is provided with the above-mentioned light emitting device.
[0043] Furthermore, a lighting device using an embodiment of the light emitting device of the present invention is also included in the scope of the present invention. Therefore, an embodiment of the lighting device of the present invention is provided with the above-mentioned light emitting device.
[0044] Since the fluorene derivative of the present invention has high hole transport properties, it can be mainly used for the hole transport layer in the EL layer of the light-emitting element. In addition, the fluorene derivative of the present invention is used for the hole transport layer to form a light-emitting element, thereby forming a light-emitting element with high luminous efficiency.
[0045] At the same time, using this light-emitting element, a light-emitting device, an electronic device, and a lighting device having low power consumption and low driving voltage can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1A and 1B Each is a diagram showing a light emitting element;
[0048] Figure 2A-2C Each is a diagram showing a light emitting element;
[0049] Figure 3A and 3B Each is a diagram showing a light emitting element;
[0050] Figure 4A and 4B Each is a diagram showing a light emitting device;
[0051] Figure 5A and 5B Each is a diagram showing a light emitting device;
[0052] Figures 6A-6D is a diagram showing an electronic device;
[0053] Figure 7 is a diagram showing an electronic device;
[0054] Figure 8 is a diagram showing a lighting device;
[0055] Fig. 9 is a diagram showing a lighting device;
[0056] Fig. 10A and 10B It is 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine 1 H-NMR spectrum;
[0057] Fig.11 is the absorption spectrum of 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine;
[0058] Fig.12 is the emission spectrum of 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine;
[0059] Fig.13is a graph showing the CV test results of 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine;
[0060] Fig.14A and 14B It is 4-phenyl-4′-[4-(9-phenylfluoren-9-yl)phenyl]triphenylamine 1 H-NMR spectrum;
[0061] Fig.15 is the absorption spectrum of 4-phenyl-4′-[4-(9-phenylfluoren-9-yl)phenyl]triphenylamine;
[0062] Fig.16 is the emission spectrum of 4-phenyl-4′-[4-(9-phenylfluoren-9-yl)phenyl]triphenylamine;
[0063] Fig.17 is a graph showing the CV test results of 4-phenyl-4′-[4-(9-phenylfluoren-9-yl)phenyl]triphenylamine;
[0064] Fig.18 It is a figure which shows the light-emitting element in Example.
[0065] Fig.19 This is a characteristic diagram showing the current density and luminance of the light-emitting element 1 and the light-emitting element 2 for comparison.
[0066] Fig. 20 1 is a characteristic diagram showing the voltage and luminance of the light-emitting element 1 and the light-emitting element 2 for comparison.
[0067] Fig.21 This is a characteristic diagram showing the luminance and current efficiency of the light-emitting element 1 and the light-emitting element 2 for comparison.
[0068] Fig. 22 is a characteristic diagram showing the current density and brightness of the light emitting element 3;
[0069] Fig.23 is a characteristic diagram showing the voltage and brightness of the light emitting element 3;
[0070] Fig.24 is a characteristic diagram showing the brightness and current efficiency of the light emitting element 3;
[0071] Fig.25 is a diagram showing the reliability test results of light emitting element 3;
[0072] Fig.26 is a characteristic diagram showing the current density and brightness of light-emitting element 4 and light-emitting element 5;
[0073] Fig. 27 is a characteristic diagram showing the voltage and brightness of light emitting element 4 and light emitting element 5;
[0074] Fig.28 is a characteristic diagram showing the brightness and current efficiency of light-emitting element 4 and light-emitting element 5;
[0075] Fig.29 is a diagram showing the reliability test results of Light Emitting Element 4 and Light Emitting Element 5;
[0076] Fig.30 is a characteristic diagram showing the current density and brightness of the light-emitting element 6 and the comparative light-emitting element 7;
[0077] Fig.31 It is a characteristic diagram showing the voltage and luminance of the light-emitting element 6 and the comparative light-emitting element 7.
[0078] Fig.32 is a characteristic diagram showing the brightness and current efficiency of the light-emitting element 6 and the comparative light-emitting element 7;
[0079] Fig.33 is a diagram showing emission spectra of Light-Emitting Element 6 and Comparative Light-Emitting Element 7;
[0080] Fig.34 is a characteristic diagram showing the current density and brightness of light-emitting elements 8 to 10;
[0081] Fig.35 is a characteristic diagram showing the voltage and brightness of light emitting element 8 to light emitting element 10;
[0082] Fig.36 is a characteristic diagram showing the brightness and current efficiency of light-emitting elements 8 to 10;
[0083] Fig.37 is a diagram showing the reliability test results of light emitting elements 8 to 10;
[0084] Fig.38 is a characteristic diagram showing the current density and brightness of the light-emitting element 11 and the comparative light-emitting element 12;
[0085] Fig.39 is a characteristic diagram showing the voltage and brightness of the light emitting element 11 and the comparison light emitting element 12;
[0086] Fig.40 is a characteristic diagram showing the brightness and current efficiency of the light-emitting element 11 and the comparative light-emitting element 12;
[0087] Fig.41 is a diagram showing emission spectra of light-emitting element 11 and comparative light-emitting element 12;
[0088] Fig.42 is a characteristic diagram showing the current density and brightness of the light emitting element 13;
[0089] Fig.43 is a characteristic diagram showing the voltage and brightness of the light emitting element 13;
[0090] Fig.44 is a characteristic diagram showing the brightness and current efficiency of the light emitting element 13;
[0091] Fig.45A and 45B It is 4-phenyl-3′-(9-phenylfluoren-9-yl)triphenylamine 1 H-NMR spectrum;
[0092] Fig.46 is a graph showing the absorption spectrum of 4-phenyl-3′-(9-phenylfluoren-9-yl)triphenylamine;
[0093] Fig.47 is a graph showing the emission spectrum of 4-phenyl-3′-(9-phenylfluoren-9-yl)triphenylamine;
[0094] Fig.48 is a characteristic diagram showing the current density and brightness of the light-emitting element 14 and the comparative light-emitting element 15;
[0095] Fig.49 is a characteristic diagram showing the voltage and brightness of the light emitting element 14 and the comparison light emitting element 15;
[0096] Fig.50 is a characteristic diagram showing the brightness and current efficiency of the light-emitting element 14 and the comparative light-emitting element 15;
[0097] Best Mode for Carrying Out the Invention
[0098] The following will describe the embodiments of the present invention with reference to the accompanying drawings. It should be noted that the present invention is not limited to the following description, and those skilled in the art can easily understand that various changes and improvements can be made without departing from the purpose and scope of the present invention. Therefore, the present invention is not limited to the following description in the embodiments.
[0099] (Implementation Method 1)
[0100] In Embodiment 1, a fluorene derivative according to one embodiment of the present invention is described.
[0101] The fluorene derivative according to one embodiment of the present invention is a fluorene derivative represented by the general formula (G1).
[0102] [Chemical formula 9]
[0103]
[0104] In the formula, R 1 -R 8independently represent any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted biphenyl group. 1 -α 4 independently represent any substituted or unsubstituted arylene group having 6 to 12 carbon atoms. 1 and Ar 2 independently represents any aromatic group having 6 to 13 ring carbon atoms, Ar 3 represents an alkyl group having 1 to 6 carbon atoms or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms. J, k, m, and n independently represent 0 or 1. It should be noted that at least one of J and k is 1.
[0105] When R 1 -R 8 ,α 1 To α 4 ,Ar 1 ,Ar 2 ,Ar 3 When there is a substituent, the substituent may be, for example, an alkyl group, such as a methyl group, an ethyl group, a propyl group, a pentyl group or a hexyl group, or an aryl group, such as a phenyl group or a biphenyl group. Alternatively, the substituents may be linked to each other to form a ring (e.g., a biphenyl group and an Ar 1 or Ar 2 The fluorene group forms a ring (for 9,9′-spirofluorenyl), or the hexyl group forms a ring (for cyclohexyl).
[0106] It is considered that when an alkyl group is used in the general formula (G1), solubility in an organic solvent is improved; therefore, when an element is formed by a wet process using the material, the use of a material having an alkyl group enables easy production of the element, which is preferred.
[0107] For R in the general formula (G1) 1 To R 8 , may be a hydrogen atom, an alkyl group such as methyl, ethyl, propyl, pentyl or hexyl, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted aryl group such as biphenyl. Structural formulas (R-1) to (R-9) are specifically given.
[0108] [Chemical formula 10]
[0109]
[0110] For α in the general formula (G1) 1 To α 4 , which may be a substituted or unsubstituted phenylene group. Specific structural formulas (α-1) to (α-3) are given.
[0111] [Chemical formula 11]
[0112]
[0113] For Ar in the general formula (G1) 1 and Ar 2 , may be a substituted or unsubstituted phenyl, a substituted or unsubstituted biphenyl, a substituted or unsubstituted naphthyl, a substituted or unsubstituted fluorenyl, or a substituted or unsubstituted aryl, such as a spirofluorenyl. Specific structural formulas (Ar-1) to (Ar-6) are given. In the following (Ar-4), the biphenyl group and Ar 1 or Ar 2 The fluorenyl group forms a ring, namely 9,9′-spirofluorenyl.
[0114] In this case, when the fused ring group represented by (Ar-2) or (Ar-3) is used, the carrier transport performance is improved, which is preferred. Also in this case, when the α between the fused ring group and the nitrogen atom is 1 or α 2 When π is 1, the molecule can maintain a wider band gap (Bg), which is preferred. In addition, as shown in (Ar-5), the structure bonded by σ bonds makes it difficult for the conjugation from the nitrogen atom to extend, and the Bg and T1 energy levels are high. Therefore, it is considered that the material can be used as a layer material adjacent to the light-emitting layer in a light-emitting element with a shorter wavelength, or as a doping material for the light-emitting layer, which is preferred. In addition, when a condensed ring group having a large and rigid molecular weight is used, such as (Ar-2), (Ar-3) or (Ar-4), thermophysical properties such as the glass transition temperature (T g ) is improved, which is preferred.
[0115] [Chemical formula 12]
[0116]
[0117] For Ar in the general formula (G1) 3 , can be an alkyl group, such as methyl, ethyl, propyl, pentyl or hexyl, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted aryl group, such as biphenyl. Specific structural formulas (Ar3-1) to (Ar3-8) are given.
[0118] [Chemical formula 13]
[0119]
[0120] Fluorene derivatives represented by structural formulae (100) to (123) or structural formulae (150) to (173) are given as specific examples of the fluorene derivative represented by general formula (G1). However, embodiments of the present invention are not limited thereto.
[0121] [Chemical formula 14]
[0122]
[0123] [Chemical formula 15]
[0124]
[0125] [Chemical formula 16]
[0126]
[0127] [Chemical formula 17]
[0128]
[0129] [Chemical formula 18]
[0130]
[0131] [Chemical formula 19]
[0132]
[0133] [Chemical formula 20]
[0134]
[0135] [Chemical formula 21]
[0136]
[0137] Various reactions can be applied to the synthesis method of the fluorene derivative of the embodiment of the present invention. For example, the fluorene derivative represented by the general formula (G1) in the embodiment of the present invention can be synthesized by the synthesis reaction described below. It should be noted that the synthesis method of the fluorene derivative in the embodiment of the present invention is not limited to the following synthesis method.
[0138] <Synthesis Method 1 of Fluorene Derivative Represented by General Formula (G1)>
[0139] As shown in scheme (A-1), a 1-halogenobiphenyl derivative (a1) is lithiated or converted into a Grignard reagent and reacted with a benzoyl derivative (a2) for dehydroxylation (dehydroxilation), thereby obtaining a halogenoarylfluorene derivative (a3).
[0140] [Chemical formula 22]
[0141]
[0142] The halogen-containing aryl compound in the scheme (A-1) is activated, reacted with a benzoyl derivative to form a phenol derivative, and then dehydroxylated by acid addition to obtain a fluorene derivative.
[0143] Lithiation reactions using alkyl lithium reagents or reactions using active magnesium to obtain Grignard reagents can be used as examples of activation. n-Butyl lithium, tert-butyl lithium, and methyl lithium are examples of alkyl lithiums. Hydrochloric acid can be used as an acid. Ethers such as diethyl ether, or tetrahydrofuran (THF) can be used as dehydration solvents.
[0144] As shown in Scheme (A-2), a diarylamine derivative (a6) can be obtained by coupling a halogenated aromatic hydrocarbon derivative (a4) and an arylamine derivative (a5).
[0145] [Chemical formula 23]
[0146]
[0147] As shown in Scheme (A-3), a fluorene derivative represented by the above general formula (G1) can be obtained by coupling a halogenated arylfluorene derivative (a3) and a diarylamine derivative (a6).
[0148] [Chemical formula 24]
[0149]
[0150] It should be noted that X in the above schemes (A-1) to (A-3) 1 ,X 2 or X 3 is a halogen, preferably bromine or iodine, more preferably iodine due to high reactivity.
[0151] In schemes (A-2) and (A-3), there are various reaction conditions for the coupling reaction of an aryl compound containing a halogen group and an aryl compound containing an amine (aryl primary amine compound or aryl secondary amine compound). As an example, a synthesis method using a metal catalyst in the presence of a base can be used.
[0152] The case of performing the Buchwald-Hartwig reaction in schemes (A-2) and (A-3) is shown. A palladium catalyst can be used as a metal catalyst, and a mixture of a palladium complex and its ligand can be used as a palladium catalyst. Examples of palladium catalysts such as di(dibenzylideneacetone)palladium(0) and palladium acetate(II) are given. Tri-tert-butylphosphine, tri-n-hexylphosphine, tricyclohexylphosphine, 1,1-bis(diphenylphosphino)ferrocene (abbreviation: DPPF) and the like are given as ligands. Organic bases such as sodium tert-butoxide and inorganic bases such as potassium carbonate are given as substances that can be used as bases. In addition, the above reaction is preferably carried out in a solution, and toluene, xylene and benzene and the like can be used as solvents in the above reaction. However, the catalysts, ligands, bases and solvents that can be used are not limited thereto. In addition, the reaction is preferably carried out under an inert atmosphere such as nitrogen and argon.
[0153] The case of performing Ullmann reaction in schemes (A-2) and (A-3) is shown. A copper catalyst can be used as a metal catalyst, and cuprous iodide (I) and copper acetate (II) are given as copper catalysts. An inorganic base, such as potassium carbonate, is given as an example of a substance that can be used as a base. The above reaction is preferably carried out in a solution, and 1,3-dimethyl-3,4,5,6-tetrahydro-2 (1H)-pyrimidone (abbreviation: DMPU), toluene, xylene and benzene are given as solvents that can be used in the above reaction. But the catalyst, ligand, base and solvent that can be used are not limited thereto. In addition, the reaction is preferably carried out under an inert atmosphere such as nitrogen, argon.
[0154] It should be noted that a high boiling point solvent such as DMPU or xylene is preferably used because the target substance can be obtained in a shorter time and at a higher yield by the Ullmann reaction when the reaction temperature is higher than or equal to 100° C. Specifically, DMPU is more preferred because the reaction temperature is more preferably higher than or equal to 150° C.
[0155] <Synthesis Method 2 of Fluorene Derivative Represented by General Formula (G1)>
[0156] For example, as shown in Scheme (B-1), a halogenated arylfluorene derivative (a3) and an arylamine derivative (a5) are coupled to obtain a diarylamine derivative having a fluorenyl group (b1).
[0157] [Chemical formula 25]
[0158]
[0159] As shown in Scheme (B-2), a fluorene derivative represented by the above general formula (G1) can be obtained by coupling a diarylamine derivative (b1) containing a fluorenyl group and a halogenated aromatic hydrocarbon derivative (a4).
[0160] [Chemical formula 26]
[0161]
[0162] It should be noted that X in the above schemes (B-1) and (B-2) 2 or X 3 It is a halogen, preferably bromine or iodine, and more preferably iodine due to its high reactivity.
[0163] In the schemes (B-1) and (B-2)+, there are various reaction conditions for the coupling reaction of the aryl compound containing a halogen group and the aryl compound containing an amine (aryl primary amine compound or aryl secondary amine compound). As an example, a synthesis method using a metal catalyst in the presence of a base can be used.
[0164] The Butchward-Hartwig reaction and the Ullmann reaction can be carried out in schemes (B-1) and (B-2) in a similar manner to schemes (A-2) and (A-3).
[0165] <Synthesis Method 3 of Fluorene Derivative Represented by General Formula (G1)>
[0166] For example, as shown in Scheme (C-1), a halogenated arylfluorene derivative (c1) is lithiated or converted into a Grignard reagent and reacted with an organic boronic acid to obtain an arylboronic acid derivative (c2) having a fluorenyl group (note that J represents 1).
[0167] [Chemical formula 27]
[0168]
[0169] As shown in Scheme (C-2), the triarylamine derivative (c3) is halogenated to give a halogenated triarylamine derivative (c4).
[0170] [Chemical formula 28]
[0171]
[0172] As shown in Scheme (C-3), a fluorene derivative represented by the above general formula (G1) can be obtained by coupling an arylboronic acid derivative (c2) containing a fluorenyl group and a halogenated triarylamine derivative (c4).
[0173] [Chemical formula 29]
[0174]
[0175] It should be noted that k represents 1 in the schemes (C-2) and (C-3).
[0176] X in the above schemes (C-1) to (C-3) 4 or X 5 It is a halogen, preferably bromine or iodine, and more preferably iodine due to its high reactivity.
[0177] The reaction of using an aromatic compound containing a halogen group to obtain an aromatic compound containing a boronic acid group (or an organic boron group) in Scheme (C-1) has various reaction conditions. 1 To R 8 represents hydrogen or an alkyl group.
[0178] As an example of the reaction, after the aryl compound containing the halogen group is lithiated using an alkyl lithium reagent, a boron reagent is added to carry out boron oxidation or organoboration of the aryl compound containing the halogen group. As the alkyl lithium reagent, n-butyl lithium or methyl lithium etc. can be used. As the boron reagent, trimethyl borate or isopropyl borate etc. can be used. Ethers such as diethyl ether or tetrahydrofuran (THF) can be used as dehydrating solvents. Alternatively, a Grignard reagent with active magnesium can be used instead of a lithiation reagent.
[0179] The halogenation reaction in scheme (C-2) has a variety of reaction conditions. For example, a reaction using a halogenating agent in the presence of a polar solvent can be used. N-bromosuccinimide (abbreviation: NBS), N-iodosuccinimide (abbreviation: NIS), bromine, iodine or potassium iodide etc. can be used as a halogenating agent. Since it can be synthesized at low cost, bromine is preferably used as a halogenating agent. Iodine is preferably used as a halogenating agent, because when the generated substance is used as a source in the subsequent reaction, the reaction can be carried out more easily (the part replaced by iodine has a higher activity). It should be noted that k is 1 in scheme (C-2), and the halogenation reaction occurs specifically in the para position of the amine.
[0180] The coupling reaction of the aryl compound containing a halogen group and the aryl compound containing a boronic acid (arylboronic acid) in Scheme (C-3) has various reaction conditions. As one example, a synthesis method using a metal catalyst in the presence of a base can be used.
[0181] In scheme (C-3), the case of adopting Suzuki-Miyaura reaction is described. A palladium catalyst such as a mixture of a palladium complex and its ligand can be used as a metal catalyst. Palladium acetate (II), tetrakis (triphenylphosphine) palladium (0) and bis (triphenylphosphine) palladium dichloride (II) are given as palladium catalysts. Tri (o-tolyl) phosphine, triphenylphosphine and tricyclohexylphosphine are given as ligands. In addition, organic bases such as sodium tert-butoxide and inorganic bases such as potassium carbonate are given as bases. The reaction is preferably carried out in a solution, and a mixed solvent of toluene and water can be used; a mixed solvent of toluene, alcohols such as ethanol and water; a mixed solvent of xylene and water; a mixed solvent of xylene, alcohols such as ethanol and water; a mixed solvent of benzene and water; a mixed solvent of benzene, alcohols such as ethanol and water; a mixed solvent of ethers such as ethylene glycol dimethyl ether and water, etc. are used as solvents. However, the catalysts, ligands, bases and solvents that can be used are not limited to this. Alternatively, in the above scheme, an organoboron compound of an aryl derivative, arylaluminum, arylazirconium, arylazinc or arylatin compound may be used instead of arylboronic acid. In addition, the reaction is preferably carried out under an inert atmosphere such as nitrogen or argon.
[0182] (Implementation Method 2)
[0183] In Embodiment 2, a light-emitting element in which the fluorene derivative according to the embodiment of the present invention described in Embodiment 1 is used for forming a hole transport layer is described.
[0184] The light-emitting element of Embodiment 2 includes a first electrode serving as an anode, a second electrode serving as a cathode, and an EL layer disposed between the first electrode and the second electrode. It should be noted that when a voltage is applied to each electrode so that the first electrode has a higher potential than the second electrode, the light-emitting element of Embodiment 2 can emit light.
[0185] In addition, the EL layer of the light-emitting element in embodiment 2 includes a first layer (hole injection layer), a second layer (hole transport layer), a third layer (light-emitting layer), a fourth layer (electron transport layer) and a fifth layer (electron injection layer) starting from the first electrode side.
[0186] Combination Figure 1A and 1B The structure of the light-emitting element in Embodiment 2 is described. The substrate 101 serves as a support of the light-emitting element. For example, glass, quartz, or plastic can be used as the substrate 101.
[0187] It should be noted that although the above-mentioned substrate 101 can be retained in the product light-emitting device or electronic device using the light-emitting element of the embodiment of the present invention, the substrate 101 is only used as a support for the light-emitting element during the processing of the light-emitting element and is not retained in the terminal product.
[0188] For the first electrode 102 formed on the substrate 101, it is preferred to use a metal, alloy, conductive compound or a mixture thereof having a high work function (specifically, a work function greater than or equal to 4.0 eV). Specific examples are given below: indium tin oxide (ITO), indium tin oxide containing silicon or silicon oxide, indium zinc oxide (IZO), indium oxide containing tungsten oxide and zinc oxide (IWZO). In addition, there are gold (Au), platinum (Pt), nickel (Ni), tungsten (W), chromium (Cr), molybdenum (Mo), iron (Fe), cobalt (Co), copper (Cu), palladium (Pd), titanium (Ti), metal nitride materials (such as titanium nitride), etc. It should be noted that in the present invention, since the first layer 111 in the EL layer 103 in contact with the first electrode 102 contains a composite material that is conducive to hole injection, regardless of the work function of the first electrode 102, any known material can be used as long as the material can be used as an electrode material (for example, metals, alloys, conductive compounds and mixtures thereof, and elements belonging to Group 1 or Group 2 of the periodic table).
[0189] These materials are generally formed by sputtering. For example, an indium oxide-zinc oxide (IZO) film can be formed by a sputtering method using a target in which 1-20 wt% zinc oxide is added to indium oxide; an indium oxide film containing tungsten oxide and zinc oxide can be formed by a sputtering method using a target in which 0.5-5 wt% tungsten oxide and 0.1-1 wt% zinc oxide are added to indium oxide. Alternatively, a vacuum evaporation method, a coating method, an inkjet method, a spin coating method, or the like can be used.
[0190] In addition, in the EL layer 103 formed on the first electrode 102, when the following composite material is used for the first layer 111 formed in contact with the first electrode 102, any of a variety of metals, alloys, conductive compounds, and mixtures thereof can be used as a material for the first electrode 102 regardless of the work function. For example, aluminum (Al), silver (Ag), aluminum-containing alloys (AlSi), etc. can also be used.
[0191] Alternatively, any element belonging to Group 1 and 2 of the periodic table, i.e., alkali metals such as lithium (Li) and cesium (Cs), alkaline earth metals such as magnesium (Mg), calcium (Ca) and strontium (Sr), alloys containing them (e.g., MgAg and AlLi), rare earth metals such as europium (Eu) and ytterbium (Yb), alloys containing them, etc., materials having a low work function can be used.
[0192] Note that when the first electrode 102 is formed using an alkali metal, an alkaline earth metal, or an alloy thereof, a vacuum evaporation method or a sputtering method can be used. Alternatively, when a silver paste or the like is used, a coating method or an inkjet method can be used.
[0193] The EL layer 103 formed over the first electrode 102 can be formed using a known material, and a low molecular compound or a high molecular compound can be used. Note that a substance forming the EL layer 103 is not limited to an organic compound, and may contain part of an inorganic compound.
[0194] The EL layer 103 is formed by stacking a hole injection layer containing a substance with a high hole injection property, a hole transport layer containing a substance with a high hole transport property, a light emitting layer containing a light emitting substance, an electron transport layer containing a substance with a high electron transport property, and an electron injection layer containing a substance with a high electron injection property in appropriate combination.
[0195] It should be noted that Figure 1A The EL layer 103 shown in the figure includes a first layer (hole injection layer) 111, a second layer (hole transport layer) 112, a third layer (light-emitting layer) 113, a fourth layer (electron transport layer 114) and a fifth layer (electron injection layer) 115 which are stacked in this order from the first electrode 102 side.
[0196] The first layer 111 (hole injection layer) is a hole injection layer containing a substance having a high hole injection property. As a substance having a high hole injection property, molybdenum oxide, titanium oxide, vanadium oxide, rhenium oxide, ruthenium oxide, chromium oxide, zirconium oxide, hafnium oxide, tantalum oxide, silver oxide, tungsten oxide, or manganese oxide can be used. Alternatively, a phthalocyanine-based compound such as phthalocyanine (abbreviation: H 2 Pc) or copper (II) phthalocyanine (abbreviation: CuPc) or vanadyl phthalocyanine (abbreviation: VOPc) as the low molecular weight organic compound. It should be noted that the fluorene derivative of the embodiment of the present invention described in Embodiment 1 can also be used in a similar manner.
[0197] In addition, as examples of low molecular weight organic compounds, there are aromatic amine compounds such as 4,4',4"-tris(N,N-diphenylamino)triphenylamine (abbreviation: TDATA), 4,4',4"-tris[N-(3-methylphenyl)-N-phenylamino]triphenylamine (abbreviation: MTDATA), 4,4'-bis[N-(4-diphenylaminophenyl)-N-phenylamino]biphenyl (abbreviation: DPAB), 4,4'-bis(N-{4-[N'-(3-methylphenyl)-N'-phenylamino]phenyl}-N-phenylamino)biphenyl (abbreviation: DPAB), The present invention also includes 1,3,5-tris[N-(4-diphenylaminophenyl)-N-phenylamino]benzene (abbreviation: DNTPD), 1,3,5-tris[N-(4-diphenylaminophenyl)-N-phenylamino]benzene (abbreviation: DPA3B), 3-[N-(9-phenylcarbazole-3-yl)-N-phenylamino]-9-phenylcarbazole (abbreviation: PCzPCA1), 3,6-di[N-(9-phenylcarbazole-3-yl)-N-phenylamino]-9-phenylcarbazole (abbreviation: PCzPCA2) and 3-[N-(1-naphthyl)-N-(9-phenylcarbazole-3-yl)amino]-9-phenylcarbazole (abbreviation: PCzPCN1), etc. It should be noted that the carbazole derivatives of the present embodiment described in Embodiment 1 can also be used in a similar manner.
[0198] In addition, any polymer compound (e.g., an oligomer, a dendrimer, or a polymer) may be used. For example, examples of the polymer compound are poly(N-vinylcarbazole) (abbreviation: PVK), poly(4-vinyltriphenylamine) (abbreviation: PVTPA), poly[N-(4-{N′-[4-(4-diphenylamino)phenyl]phenyl-N′-phenylamino}phenyl)methacrylamide] (abbreviation: PTPDMA), or poly[N,N′-di(4-butylphenyl)-N,N′-di(phenyl)benzidine] (abbreviation: poly-TPD), etc. Alternatively, a polymer compound to which an acid is added may be used, for example, poly(3,4-ethylenedioxythiophene) / poly(styrenesulfonic acid) (PEDOT / PSS) or polyaniline / poly(styrenesulfonic acid) (PAni / PSS).
[0199] In addition, a composite material obtained by mixing an acceptor substance into a substance having high hole transport properties can be used for the first layer 111. Using such a high hole transporting substance containing an acceptor substance, the material used to form the electrode can be selected without considering the work function. In other words, not only a high work function material can be used for the first electrode 102, but also a low work function material can be used as the first electrode 102. Such a composite material can be formed by co-depositing a substance having high hole transport properties and a substance having acceptor properties. It should be noted that in this specification, the term "composite" not only refers to a state in which two materials are simply mixed, but also refers to a state in which multiple materials are mixed and electrons are transferred between the materials.
[0200] As the organic compound for the composite material, various compounds can be used, such as aromatic amine compounds, carbazole derivatives, aromatic hydrocarbons and polymer compounds (e.g., oligomers, dendrimers or polymers). The organic compound for the composite material is preferably an organic compound with high hole transport properties. Specifically, it is preferred to use an organic compound with a hole mobility greater than or equal to 10 -6 cm 2 / V. However, any substance other than the above substances may be used as long as it is a substance having a hole transport property higher than an electron transport property. Specific examples of organic compounds that can be used for the composite material are as follows.
[0201] For example, as organic compounds that can be used for the composite material, there are: aromatic amine compounds such as MTDATA, TDATA, DPAB, DNTPD, DPA3B, PCzPCA1, PCzPCA2, PCzPCN1, 4,4′-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB or α-NPD) and N,N′-di(3-methylphenyl)-N,N′-diphenyl-[1,1′-biphenyl]-4,4′-diamine (abbreviation: TPD); and carbazole derivatives such as 4,4′-di(N-carbazolyl)biphenyl (abbreviation: CBP), 1,3,5-tri[4-(N-carbazolyl)phenyl]benzene (abbreviation: TCPB), 9-[4-(N-carbazolyl)]phenyl-10-phenylanthracene (abbreviation: CzPA) and 1,4-di[4-(N-carbazolyl)phenyl-2,3,5,6-tetraphenylbenzene. It should be noted that the carbazole derivatives of the embodiments of the present invention described in Embodiment 1 can also be used in a similar manner.
[0202] In addition, the aromatic hydrocarbon compounds include, for example, 2-tert-butyl-9,10-di(2-naphthyl)anthracene (abbreviation: t-BuDNA), 2-tert-butyl-9,10-di(1-naphthyl)anthracene, 9,10-di(3,5-diphenylphenyl)anthracene (abbreviation: DPPA), 2-tert-butyl-9,10-di(4-phenylphenyl)anthracene (abbreviation: t-BuDBA), 9,10-di(2-naphthyl)anthracene (abbreviation: DNA), 9,10-diphenylanthracene (abbreviation: DPAnth), 2-tert-butylanthracene (abbreviation: t-BuAnth), 9,10-di(4-methyl-1-naphthyl)anthracene (abbreviation: DMNA), 9,10-di[2-(1-naphthyl)phenyl)-2-tert-butylanthracene, 9,10-di[2-(1-naphthyl)phenyl]anthracene and 2,3,6,7-tetramethyl-9,10-di(1-naphthyl)anthracene.
[0203] In addition, the aromatic hydrocarbon compounds include, for example, 2,3,6,7-tetramethyl-9,10-di(2-naphthyl)anthracene, 9,9'-bianthracene, 10,10'-diphenyl-9,9'-bianthracene, 10,10'-di(2-phenylphenyl)-9,9'-bianthracene, 10,10'-di[(2,3,4,5,6-pentaphenyl)phenyl]-9,9'-bianthracene, anthracene, tetracene, rubrene, perylene, 2,5,8,11-tetra(tert-butyl)perylene, pentacene, coronene, 4,4'-bis(2,2-diphenylvinyl)biphenyl (abbreviation: DPVBi), and 9,10-bis[4-(2,2-diphenylvinyl)phenyl]anthracene (abbreviation: DPVPA).
[0204] As the substance having an acceptor property, there can be given an organic compound such as 7,7,8,8-tetracyano-2,3,5,6-tetrafluoroquinodimethane (abbreviation: F 4 -TCNQ) and chloranil, and transition metal oxides. In addition, there are oxides of metals of the 4th to 8th groups of the periodic table. Specifically, vanadium oxide, niobium oxide, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide and rhenium oxide are preferably used because they have high electron accepting properties. Among them, molybdenum oxide is particularly preferred because it is easy to handle due to its stability in air and its low hygroscopicity.
[0205] It should be noted that for the first layer 111, a composite material formed by any of the above-mentioned polymer compounds such as PVK, PVTPA, PTPDMA or poly-TPD and any of the above-mentioned acceptor substances can be used. It should be noted that a composite material formed by combining the carbazole compound of the embodiment of the present invention described in Embodiment 1 with the above-mentioned substance having acceptor properties can also be used for the first layer 111.
[0206] The second layer 112 is a hole transport layer containing a substance having a high hole transport property. It should be noted that the fluorene derivative of the embodiment of the present invention described in Embodiment 1 can also be used for the second layer 112 in Embodiment 2. Since the above-mentioned fluorene derivative of the embodiment of the present invention has a wide band gap, the second layer 112 formed using the fluorene derivative is difficult to absorb the excitation energy generated in the third layer (light-emitting layer) 113 adjacent to the second layer 112, and the excitons are effectively confined in the light-emitting layer. Thus, a high-efficiency light-emitting element can be obtained.
[0207] In addition, the fluorene derivative of the embodiment of the present invention described in Embodiment 1 can be used for both the first layer 111 and the second layer 112. In this case, the element can be easily formed and the use efficiency of the material can be improved. In addition, since the energy diagrams of the first layer 111 and the second layer 112 are the same or similar, carriers can be easily transferred between the first layer 111 and the second layer 112.
[0208] The third layer 113 is a layer containing a substance having a high light-emitting property. A low-molecular organic compound described below can be used for the third layer 113. It should be noted that since the fluorene derivative of the embodiment of the present invention described in Embodiment 1 has a light-emitting property, the fluorene derivative can also be used as a light-emitting material.
[0209] As the light-emitting substance, for example, a fluorescent compound that emits fluorescence or a phosphorescent compound that emits phosphorescence can be used.
[0210] Fluorescent compounds that can be used for the light-emitting layer 113, for example, light-emitting substances that emit blue light include N,N'-di[4-(9H-carbazole-9-yl)phenyl]-N,N'-diphenylstilbene-4,4'-diamine (abbreviation: YGA2S), 4-(9H-carbazole-9-yl)-4'-(10-phenyl-9-anthracenyl)triphenylamine (abbreviation: YGAPA), etc.
[0211] The green emitting materials include N-(9,10-diphenyl-2-anthracenyl)-N,9-diphenyl-9H-carbazole-3-amine (abbreviation: 2PCAPA), N-[9,10-di(1,1′-biphenyl-2-yl)-2-anthracenyl]-N,9-diphenyl-9H-carbazole-3-amine (abbreviation: 2PCABPhA), N-(9,10-diphenyl-2-anthracenyl)-N,N′,N′-triphenyl-1,4-phenylenediamine (abbreviation: 2D PAPA), N-[9,10-di(1,1′-biphenyl-2-yl)-2-anthracenyl]-N,N′,N′-triphenyl-1,4-phenylenediamine (abbreviation: 2DPABPhA), 9,10-di(1,1′-biphenyl-2-yl)]-N-[4-(9H-carbazole-9-yl)phenyl]-N-phenylanthracen-2-amine (abbreviation: 2YGABPhA), N,N,9-triphenylanthracen-9-amine (abbreviation: DPhAPhA), etc.
[0212] Examples of yellow-light-emitting materials include rubrene, 5,12-di(1,1′-biphenyl-4-yl)-6,11-diphenyltetracene (abbreviation: BPT), etc. Examples of red-light-emitting materials include N,N,N′,N′-tetrakis(4-methylphenyl)tetracene-5,11-diamine (abbreviation: p-mPhTD), 7,14-diphenyl-N,N,N′,N′-tetrakis(4-methylphenyl)acenaphtho[1,2-a]fluoranthene-3,10-diamine (abbreviation: p-mPhAFD), etc.
[0213] Phosphorescent compounds that can be used as the light-emitting layer 113 include, for example, tetrakis(1-pyrazolyl)borate di[2-(4′,6′-difluorophenyl)pyridine-N,C 2′ ]iridium(III) (abbreviation: FIr6), bis[2-(4′,6′-difluorophenyl)pyridine-N,C 2′ ]iridium(III) complex (abbreviation: FIrpic), picolinic acid di{2-[3′,5′-bis(trifluoromethyl)phenyl]pyridine-N,C 2 '}Iridium(III) (Abbreviation: Ir(CF 3 ppy) 2 (pic)) or acetylacetonate di[2-(4′,6′-difluorophenyl)pyridine-N,C 2 '] iridium (III) (abbreviation: FIr (acac)) and the like. The substances used for green light emission are tris (2-phenylpyridine-N,C 2′ )Iridium(III) (Abbreviation: Ir(ppy) 3 ), acetylacetonate di(2-phenylpyridine-N,C 2′ )Iridium(III) (Abbreviation: Ir(ppy)2 (acac)), bis(1,2-diphenyl-1H-benzimidazole)iridium(III) acetylacetonate (abbreviation: Ir(pbi) 2 (acac)), or bis(benzo[h]quinolinyl)iridium(III)acetylacetonate (abbreviation: Ir(bzq) 2 (acac) etc. The substances used for yellow light emission are acetylacetonate di(2,4-diphenyl-1,3-oxazol-N,C 2 ') Iridium(III) (Abbreviation: Ir(dpo) 2 (acac)), bis[2-(4'-(pentafluorophenylphenyl)pyridine]iridium(III) acetylacetonate (abbreviation: Ir(p-PF-ph) 2 (acac)), or acetylacetonate di(2-phenylbenzothiazole-N,C 2 ') Iridium (III) (Abbreviation: Ir(bt) 2 (acac) etc. The substances used for orange light emission include tris(2-phenylquinoline-N,C 2 ') Iridium (III) (Abbreviation: Ir(pq) 3 ), or acetylacetonate di(2-phenylquinoline-N,C 2 ') Iridium (III) (Abbreviation: Ir(pq) 2 (acac) etc. The substance used for red light emission is an organic metal complex, for example, acetylacetonate di[2-(2′-benzo[4,5-a]thienyl)pyridine acid-N,C 3 ') Iridium(III) (Abbreviation: Ir(btp) 2 (acac)), acetylacetonate di(1-phenylisoquinoline)-N,C 2 ') Iridium (III) (Abbreviation: Ir(piq) 2 (acac), (acetylacetonato)bis[2,3-bis(4-fluorophenyl)quinoxaline]iridium(III) (abbreviation: Ir(Fdpq) 2 (acac)) or 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum (II) (abbreviation: PtOEP), etc. In addition, rare earth metal complexes such as tris(acetylacetonate)(monophenanthroline)terbium (III) (abbreviation: Tb(acac) 3 (Phen), tris(1,3-diphenyl-1,3-propanedionato)(monophenanthroline)europium(III) (abbreviation: Eu(DBM) 3 (Phen)) or tris[1-(2-thenoyl)-3,3,3-trifluoroacetonato](monophenanthroline)europium(III) (abbreviation: Eu(TTA)3 (Phen)) exhibits light emission from rare earth metal ions (electron transfer between different multiplets); thus such rare earth metal complexes can be used as phosphorescent compounds.
[0214] The third layer 113 may have a structure in which the above-mentioned substance with high luminescent properties is dispersed in another substance. It should be noted that in the case of dispersion, the concentration of the dispersed substance (dopant) is preferably less than or equal to 20% by mass of the total amount. In addition, known substances can be used as dispersed substances (host materials) with luminescent properties. It is preferred to use a substance whose lowest unoccupied molecular orbital energy level (LUMO energy level) is shallower than the luminescent substance (smaller absolute value) and whose highest occupied molecular orbital energy level (HOMO energy level) is deeper than the luminescent substance (larger absolute value). In addition, it is preferred that the band gap (Bg: the difference between the HOMO energy level and the LUMO energy level) of the host material is greater than the Bg of the dopant with luminescent properties. In addition, when the light emitted by the dopant is fluorescence at the S1 energy level, the dopant is preferably higher than the host material, and when the light emitted by the dopant is phosphorescence at the T1 energy level, the dopant is preferably higher than the host material.
[0215] Specifically, the metal complexes include tris(8-quinolinolato)aluminum(III) (abbreviation: Alq), tris(4-methyl-8-quinolinolato)aluminum(III) (abbreviation: Almq 3 ), bis(10-hydroxybenzo[h]-quinolinolato)beryllium(II) (abbreviation: BeBq 2 ), bis(2-methyl-8-hydroxyquinoline)(4-phenylphenol)aluminum(III) (abbreviation: BAlq), bis(8-hydroxyquinoline)zinc(II) (abbreviation: Znq), bis[2-(2-benzoxazolyl)phenol]zinc(II) (abbreviation: ZnPBO) or bis[2-(2-benzothiazolyl)phenol]zinc(II) (abbreviation: ZnBTZ).
[0216] In addition, the heterocyclic compound is 2-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-1,3,4-oxadiazole (abbreviation: PBD), 1,3-di[5-(p-tert-butylphenyl)-1,3,4-oxadiazole-2-yl]benzene (abbreviation: OXD-7), 3-(biphenyl-4-yl)-4-phenyl-5-(4-tert-butylphenyl)-1,2,4-triazole (abbreviation: TAZ), 2,2′,2″-(1,3,5-benzenetriyl)tris(1-phenyl-1H-benzimidazole) (abbreviation: TPBI), bathophenanthroline (abbreviation: BPhen) or bathocuproin (abbreviation: BCP).
[0217] Alternatively, a condensed aromatic compound such as 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA), 3,6-diphenyl-9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: DPCzPA), 9,10-di(3,5-diphenylphenyl)anthracene (abbreviation: DPPA), 9,10-di(2-naphthyl)anthracene (abbreviation: DNA), 2-tert-butyl-9,10-di(2-naphthyl)anthracene (abbreviation: t-BuDNA), 9,9'-bianthracene (abbreviation: BANT), 9,9'-(stilbene-3,3'-diyl)diphenanthrene (abbreviation: DPNS), 9,9'-(stilbene-4,4'-diyl)diphenanthrene (abbreviation: DPNS2), or 3,3',3"-(benzene-1,3,5-triyl)tripyrene (abbreviation: TPB3) may also be used.
[0218] A variety of substances can be used as the dispersed substance with luminescent properties. For example, in order to suppress crystallization, a substance that suppresses crystallization, such as rubrene, can be further added. In addition, NPB or Alq, etc. can be further added to effectively transfer energy to the substance with luminescent properties. It should be noted that the fluorene derivative of the embodiment of the present invention described in Embodiment Mode 1 can be used. By using a structure in which a substance with high luminescent properties is dispersed in another substance, the crystallization of the third layer 113 can be suppressed. In addition, concentration quenching caused by a high concentration of a substance with high luminescent properties can also be suppressed.
[0219] In addition, among the above substances, it is particularly preferable to use a substance having an electron transport property, and disperse a substance having a light-emitting property therein to form the third layer 113. Specifically, any of the above metal complexes and heterocyclic compounds; CzPA, DNA, and t-BuDNA among the above condensed aromatic compounds; and larger molecular compounds will be given below as substances that can be used for the fourth layer 114.
[0220] Alternatively, the polymer compounds given below may be used for the third layer 113 .
[0221] The luminescent materials used for blue light emission include poly(9,9-dioctylfluorene-2,7-diyl) (abbreviation: PFO), [(9,9-dioctylfluorene-2,7-diyl)-(2,5-dimethoxybenzene-1,4-diyl)] copolymer (abbreviation: PF-DMOP), {(9,9-dioctylfluorene-2,7-diyl)-[N,N′-di-(p-butylphenyl)-1,4-phenylenediamine]} copolymer (abbreviation: TAB-PFH), etc.
[0222] The luminescent materials used for green light emission include poly(p-phenylene vinylene) (abbreviation: PPV), [(9,9-dihexylfluorene-2,7-dimer)-(benzo[2,1,3]thiadiazole-4,7-diyl)] cross copolymer (abbreviation: PFBT), [(9,9-dioctyl-2,7-divinylenefluorenylene)-(2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene) cross copolymer, etc.
[0223] The luminescent materials for orange to red light emission include poly[2-methoxy-5-(2′-ethylhexyloxy)-1,4-phenylenevinylene] (abbreviation: MEH-PPV), poly(3-butylthiophene-2,5-diyl) (abbreviation: R 4 -PAT), {[9,9-dihexyl-2,7-bis(1-cyanovinylene)fluorenyl]-[2,5-bis(N,N′-diphenylamino)-1,4-phenylene]} cross copolymer, {[2-methoxy-5-(2-ethylhexyloxy)-1,4-bis(1-cyanovinylenephenylene)]-[2,5-bis(N,N′-diphenylamino)-1,4-phenylene]} cross copolymer (abbreviation: CN-PPV-DPD), etc.
[0224] The light-emitting layer 113 may be a stack of two or more layers. For example, when the first light-emitting layer and the second light-emitting layer are stacked in sequence from the hole transport layer side to form the light-emitting layer 113, the first light-emitting layer may be formed using a substance having a hole transport property as a main material, and the second light-emitting layer may be formed using a substance having an electron transport property as a main material. It is more preferred that a material having a hole transport property greater than an electron transport property is used as the main material for the first light-emitting layer and a material having an electron transport property greater than a hole transport property is used as the main material for the second light-emitting layer. With the above structure, a light-emitting site is formed between the first light-emitting layer and the second light-emitting layer, so that a more efficient element can be obtained.
[0225] When the light emitting layer having the above structure is formed using a plurality of materials, the light emitting layer may be formed by co-evaporation using a vacuum evaporation method; or by using an inkjet method, a spin coating method, a dip coating method, or the like as a method of mixing a solution.
[0226] The fourth layer 114 is an electron transport layer containing a substance having a high electron transport property. For example, a metal complex such as Alq, Almq 3 ,BeBq 2 , BAlq, Znq, ZnPBO, or ZnBTZ as low molecular weight organic compounds. Alternatively, heterocyclic compounds such as PBD, OXD-7, TAZ, TPBI, BPhen or BCP can be used instead of metal complexes. The substances mentioned here are mainly those with electron mobility greater than or equal to 10-6 cm 2 / Vs. Note that any substance other than the above substances can also be used for the electron transport layer as long as it is a substance with higher electron transport properties than hole transport properties. In addition, the electron transport layer is not limited to a single layer, and can be a stack of two or more layers formed of the above substances.
[0227] A polymer compound may also be used for the fourth layer 114. For example, a [(9,9-dihexylfluorene-2,7-diyl)-(pyridine-3,5-diyl)] copolymer (abbreviation: PF-Py) or a [(9,9-dioctylfluorene-2,7-diyl)-(2,2'-bipyridine-6,6'-diyl)] copolymer (abbreviation: PF-BPy) may be used.
[0228] The fifth layer 115 is an electron injection layer containing a substance having a high electron injection property. For the fifth layer 115, an alkali metal, an alkaline earth metal or a compound thereof, such as lithium fluoride (LiF), cesium fluoride (CsF), or calcium fluoride (CaF2) can be used. Alternatively, an electron transport material layer containing an alkali metal, an alkaline earth metal or a compound thereof can be used, specifically, an Alq layer containing magnesium (Mg) can be used. It should be noted that in this case, electrons can be injected more efficiently from the second electrode 104.
[0229] For the second electrode 104, a metal, alloy or conductive compound or a mixture thereof having a low work function (specifically, a work function of less than or equal to 3.8 eV) can be used. Elements belonging to Groups 1 and 2 of the periodic table, i.e., alkali metals such as lithium (Li) and cesium (Cs), alkaline earth metals such as magnesium (Mg), calcium (Ca) and strontium (Sr), alloys containing them (e.g., MgAg and AlLi), rare earth metals such as europium (Eu) and ytterbium (Yb), alloys containing them, etc. are given as specific examples of such cathode materials.
[0230] Note that when the second electrode 104 is formed using an alkali metal, an alkaline earth metal, or an alloy thereof, a vacuum evaporation method or a sputtering method can be used. When a silver paste or the like is used, a coating method or an inkjet method can be used.
[0231] It should be noted that by providing the fifth layer 115, any of a variety of conductive materials such as Al, Ag, ITO and indium oxide-tin oxide containing silicon or silicon oxide can be used to form the second electrode 104 regardless of the work function. Such a conductive material film can be formed by a method such as sputtering, inkjet or spin coating.
[0232] In addition, for the formation method of the EL layer 103 in which the first layer (hole injection layer) 111, the second layer (hole transport layer) 112, the third layer (light-emitting layer) 113, the fourth layer (electron transport layer) 114, and the fifth layer (electron injection layer) 115 are sequentially stacked, any of a variety of methods can be used regardless of whether the method is a dry method or a wet method. For example, a vacuum evaporation method, an inkjet method, a spin coating method, etc. can be used. It should be noted that a different formation method can be used for each layer.
[0233] The second electrode 104 may be formed by a wet method (eg, a sol-gel method using a metal paste) instead of a dry method (eg, a sputtering method or a vacuum evaporation method).
[0234] Since holes generally flow between the first electrode 102 and the first layer (hole injection layer) 111, between the first layer (hole injection layer) 111 and the second layer (hole transport layer) 112, and between the second layer (hole transport layer) 112 and the third layer (light-emitting layer) 113, their HOMO energy levels (work functions in terms of metals) are preferably the same or almost the same, thereby reducing the carrier injection barrier between adjacent layers. Similarly, electrons generally flow between the third layer (light-emitting layer) 113 and the fourth layer (electron transport layer) 114, between the fourth layer (electron transport layer) 114 and the fifth layer (electron injection layer) 115, and between the fifth layer (electron injection layer) 115 and the second electrode 104, and their LUMO energy levels (work functions in the case of metals) are preferably the same or almost the same, thereby reducing the carrier injection barrier between adjacent layers. The difference is preferably less than or equal to 0.2 eV, and more preferably less than or equal to 0.1 eV.
[0235] It is preferred that the difference in HOMO energy level between the second layer (hole transport layer) 112 and the third layer (light-emitting layer) 113 and the difference in LUMO energy level between the third layer (light-emitting layer) 113 and the fourth layer (electron transport layer) 114 be increased so that the carriers are confined in the light-emitting layer, thereby obtaining a more efficient light-emitting element. It should be noted that in this case, when the potential barrier is too high, the driving voltage is high, which will become a burden on the element. Therefore, each difference is preferably less than or equal to 0.4 eV, more preferably less than or equal to 0.2 eV.
[0236] In the above-mentioned light-emitting element of this light-emitting embodiment, light is emitted because of the potential difference generated between the first electrode 102 and the second electrode 104 and the recombination of holes and electrons in the EL layer 103, resulting in the generation of current. Then, the emitted light is extracted through one or both of the first electrode 102 and the second electrode 104. Accordingly, one or both of the first electrode 102 and the second electrode 104 are electrodes having a light-transmitting property.
[0237] like Figure 2A As shown, when only the first electrode 102 has a light-emitting property, the emitted light is extracted from the substrate side through the first electrode 102. Alternatively, as Figure 2B As shown, when only the second electrode 104 has a light-emitting property, the emitted light is extracted from the side opposite to the substrate 101 through the second electrode 104. Figure 2C As shown, when the first electrode 102 and the second electrode 104 each have a light-emitting property, emitted light is extracted from the substrate 101 side and the side opposite to the substrate 101 through the first electrode 102 and the second electrode 104 at the same time.
[0238] The layer structure provided between the first electrode 102 and the second electrode 104 is not limited to the above structure. A structure other than the above structure may be employed as long as it includes at least the second layer 112 (hole transport layer) and the third layer 113 (light-emitting layer).
[0239] Or, if Figure 1B As shown, a structure in which the second electrode 104 as a cathode, the EL layer 103, and the first electrode 102 as an anode are stacked in the order described above on the substrate 101 may be used. It should be noted that in this case, the EL layer 103 has a structure in which the fifth layer 115, the fourth layer 114, the third layer 113, the second layer 112, the third layer 111, and the first electrode 102 are stacked in the order described above on the second electrode 104.
[0240] It should be noted that by using the light-emitting element in the present invention, a passive matrix light-emitting device or an active matrix light-emitting device in which driving of the light-emitting element is controlled by a thin film transistor (TFT) can be manufactured.
[0241] It should be noted that in the case of manufacturing an active matrix light emitting device, there is no particular restriction on the structure of the TFT. For example, a staggered TFT or an inverse staggered TFT may be appropriately used. In addition, the drive circuit formed on the TFT substrate may be formed using both an n-type TFT and a p-type TFT or using only one of the n-type TFT or the p-type TFT. Furthermore, there is no particular restriction on the crystallinity of the semiconductor film used in the TFT. An amorphous semiconductor film may be used, or a crystalline semiconductor film may be used.
[0242] In the light-emitting element described in Embodiment Mode 2, since the second layer (hole transport layer) 112 is formed using the fluorene derivative of the embodiment mode of the present invention, not only the efficiency of the element can be improved but also the power consumption can be reduced.
[0243] (Implementation method 3)
[0244] See also Figure 3A and 3BIn Embodiment 3, a mode of a light-emitting element (hereinafter referred to as a stacked element) having a structure of a plurality of stacked light-emitting units (also referred to as EL layers) is described. The light-emitting element is a stacked light-emitting element having a plurality of light-emitting units between a first electrode and a second electrode. The respective structures of the light-emitting units may be similar to those in Embodiment 2. In other words, the light-emitting element described in Embodiment 2 is a light-emitting element having one light-emitting unit. In Embodiment 3, a light-emitting element having a plurality of light-emitting units is described.
[0245] exist Figure 3A In the embodiment, the first light emitting unit 511 and the second light emitting unit 512 are stacked together between the first electrode 521 and the second electrode 522. The first electrode 521 and the second electrode 522 may be similar to those in Embodiment 2. The first light emitting unit 511 and the second light emitting unit 512 may have the same or different structures, and a structure similar to that described in Embodiment 2 may be used.
[0246] When a voltage is applied to the first electrode 521 and the second electrode 522, the charge generation layer 513 is a layer that injects electrons from one side into the light-emitting unit and injects holes from the other side into the light-emitting unit, and it can be a single-layer structure or a stacked structure of multiple layers. For the stacked structure of multiple layers, a structure in which a layer for injecting holes and a layer for injecting electrons are stacked is preferred.
[0247] For the hole-injecting layer, a semiconductor or an insulator such as molybdenum oxide, vanadium oxide, rhenium oxide, or ruthenium oxide may be used. Alternatively, the hole-injecting layer may have a structure in which an acceptor substance is added to a substance having a high hole-transporting property. The layer containing a substance having a high hole-transporting property and an acceptor substance contains 7,7,8,8-tetracyano-2,3,5,6-tetrafluoroquinodimethane (abbreviation: F 4 -TCNQ) or metal oxides such as vanadium oxide, molybdenum oxide or tungsten oxide. For substances having high hole transport properties, various compounds can be used, such as aromatic amine compounds, carbazole derivatives, aromatic hydrocarbons, high molecular weight compounds, oligomers, dendrimers and polymers. It should be noted that the fluorene derivatives of the embodiments of the present invention described in Embodiment 1 can also be used in a similar manner. It should be noted that it is preferred to use a hole mobility greater than or equal to 10 -6 cm 2 / Vs as a substance with high hole transport properties. However, any substance other than the above substances can also be used as long as it is a substance with higher hole transport properties than electron transport properties. Since the composite material of the substance with high hole transport properties and the acceptor substance has good carrier injection properties and good carrier transport properties, low voltage drive and low current drive can be achieved.
[0248] For the layer for injecting electrons, a semiconductor or an insulator, such as lithium oxide, lithium fluoride or cesium carbonate, can be used. Alternatively, the hole injection layer can have a structure in which a donor substance is added to a substance with high hole transport properties. As donor substances, alkali metals, alkaline earth metals, rare earth metals, metals of Group 13 of the periodic table, or their oxides or carbonates can be used. Specifically, lithium (Li), cesium (Cs), magnesium (Mg), calcium (Ca), ytterbium (Yb), indium (In), lithium oxide or cesium carbonate, etc. are preferably used. Alternatively, an organic compound such as tetrathiafulvalene can be used as a donor substance. The material described in Embodiment 1 can be used as a substance with high electron transport properties. It should be noted that it is preferred to use a hole mobility greater than or equal to 10 -6 cm 2 / Vs as a substance with high hole transport properties. However, any substance other than the above substances can also be used as long as it is a substance with higher electron transport properties than hole transport properties. Since the composite material of the substance with high hole transport properties and the donor substance has good carrier injection properties and good carrier transport properties, low voltage drive and low current drive can be achieved.
[0249] In addition, the electrode material described in Embodiment 2 can be used for the charge generation layer 513. For example, the charge generation layer 513 can be formed by combining a layer containing a substance having a high hole transport property and a metal oxide with a transparent conductive film. Considering light extraction efficiency, the charge generation layer 513 is preferably a highly light-transmitting layer.
[0250] In any case, the charge generation layer 513 disposed between the first light emitting unit 511 and the second light emitting unit 512 is acceptable as long as it is a layer that can inject charges into the light emitting unit from one side and inject holes into the light emitting unit from the other side when a voltage is applied to the first electrode 521 and the second electrode 522. For example, any structure of the charge generation layer 513 is acceptable as long as the charge generation layer 513 injects electrons and holes into the first light emitting unit 511 and the second light emitting unit 512, respectively, when a voltage is applied in such a manner that the potential of the first electrode is higher than the potential of the second electrode.
[0251] In Embodiment Mode 3, a light-emitting element having two light-emitting units is described, but a light-emitting element in which three or more light-emitting units are stacked may also be similarly used, such as Figure 3BAs shown. By providing a plurality of light-emitting units in the light-emitting element of embodiment 3, the light-emitting units are separated by the charge generation layer 513 between the paired electrodes, light emission in a high brightness area can be achieved while maintaining a low current density, thereby achieving long-life light emission. When the light-emitting element is used in a light-emitting device as an example of application, the voltage drop caused by the resistance of the electrode material can be reduced, thereby achieving uniform light emission over a large area. In addition, a light-emitting device with low power consumption that can be driven at a low voltage can be realized.
[0252] The light-emitting units emit light of different colors, so that the entire light-emitting element emits light of the desired color. For example, in a light-emitting element having two light-emitting units, the light emitted by the first light-emitting unit and the second light-emitting unit are made complementary, so that a light-emitting element emitting white light can be obtained as a whole. It should be noted that the word "complementary" refers to the color relationship in the achromatic color obtained when the colors are mixed. That is to say, white light can be obtained by mixing the light emitted by some substances as complementary colors. The same principle can be applied to a light-emitting element having three light-emitting units. For example, when the emission color of the first light-emitting unit is red, the emission color of the second light-emitting unit is green, and the emission color of the third light-emitting unit is blue, the light-emitting element as a whole provides white light emission.
[0253] It should be noted that this Embodiment 3 can be combined with any other Embodiments as appropriate.
[0254] (Implementation 4)
[0255] In Embodiment 4, reference is made to Figure 4A and 4B A light-emitting device including the light-emitting element of the present invention in a pixel portion is described. Figure 4A is a top view of the light emitting device. Figure 4B is along Figure 4A Cross-sectional view of the straight lines A-A' and BB'.
[0256] exist Figure 4A , reference numeral 401 indicates a driver circuit portion (source side driver circuit), reference numeral 402 indicates a pixel portion, and reference numeral 403 indicates a driver circuit portion (gate side driver circuit), which are indicated by dotted lines. Reference numeral 404 indicates a sealing substrate, reference numeral 405 indicates a sealing material, and a portion surrounded by the sealing material 405 is a space 407.
[0257] It should be noted that the lead 408 is used to transmit signals, input the signals to the source side drive circuit 401 and the gate side drive circuit 403, and receive image signals, clock signals, start signals, reset signals, etc. from a flexible printed circuit (FPC) 409, which is used as an external input terminal. Although only the FPC is shown, the FPC can be connected to a printed wiring board (PWB). The light-emitting device in this specification includes not only the light-emitting device itself, but also a light-emitting device having an FPC or PWB connected thereto.
[0258] Then, reference will be made to Figure 4B The cross-sectional structure is described. A driving circuit portion and a pixel portion are formed on an element substrate 410. In this case, a pixel in a pixel portion 402 and a source side driving circuit 401 of the driving circuit portion is shown in the figure. A CMOS circuit is formed as the source side driving circuit 401, and the circuit is a combination of an n-channel TFT 423 and a p-channel TFT 424. This driving circuit can be formed using various circuits, such as a CMOS circuit, a PMOS circuit, or an NMOS circuit. Although a driving circuit is described in Embodiment 4 as a driving-integrated device formed on a substrate, the present invention is not limited to this type, and the driving circuit can be formed outside the substrate.
[0259] The pixel portion 402 includes a plurality of pixels including a switching TFT 411, a current control TFT 412, and a first electrode 413 electrically connected to the drain of the current control TFT 412. Note that an insulator 414 is formed so as to cover an end portion of the first electrode 413.
[0260] In order to improve the coverage, it is preferable to provide the insulator 414 so that the upper end or the lower end of the insulator 414 has a curved surface with a certain curvature. For example, when a positive photosensitive acrylic resin is used as the material of the insulator 414, a curved surface with a certain curvature radius (0.2-3 micrometers) is provided only at the upper end of the insulator 414. Alternatively, the insulator 414 may be formed using a negative photosensitive material that is insoluble in an etchant by light irradiation or a positive photosensitive material that is soluble in an etchant by light irradiation.
[0261] An EL layer 416 and a second electrode 417 are formed over the first electrode 413. In this case, the first electrode 413 can be formed using any of a variety of materials such as metals, alloys, and conductive compounds, or a mixture thereof. Note that as a specific material, the materials described in Embodiment 2 as materials that can be used for the first electrode can be used.
[0262] The EL layer 416 can be formed by any of various methods such as an evaporation method using an evaporation mask, an inkjet method, and a spin coating method. The EL layer 416 is any of the structures described in Embodiment Mode 2. In addition, as another material included in the EL layer 416, a low molecular compound or a high molecular compound (including an oligomer and a dendrimer) can be used. As the material of the EL layer, not only an organic compound but also an inorganic compound can be used.
[0263] The second electrode 417 can be formed using any of a variety of metals, alloys, and conductive compounds or mixtures thereof. Among such materials, when the second electrode 417 is used as a cathode, metals, alloys, and conductive compounds or mixtures thereof having a low work function (work function is less than or equal to 3.8 eV) are preferably used. Elements of Group 1 or 2 of the periodic table, i.e., alkali metals such as lithium (Li) or cesium (Cs), alkaline earth metals such as magnesium (Mg), calcium (Ca), or strontium (Sr), alloys containing any of them (e.g., MgAg and AlLi), etc. are given as examples.
[0264] It should be noted that when the light generated in the EL layer 416 is transmitted through the second electrode 417, the second electrode 417 can be formed by stacking a thin metal film and a transparent conductive film (indium oxide-tin oxide (ITO), indium oxide-tin oxide containing silicon or silicon oxide, indium oxide-zinc oxide (IZO), or indium oxide containing tungsten oxide and zinc oxide, etc.).
[0265] The sealing substrate 404 is attached to the element substrate 410 with the sealant 405; therefore, the light emitting element 418 is provided in a space 407 surrounded by the element substrate 410, the sealing substrate 404, and the sealant 405. It should be noted that the space 407 is filled with a filler such as an inert gas (such as nitrogen or argon) or the sealing material 405.
[0266] Note that an epoxy resin is preferably used as the sealant 405. The material used for this purpose is preferably a material that does not allow moisture or oxygen to pass through. As a material for forming the sealing substrate 404, a glass substrate, a quartz substrate, or a plastic substrate composed of glass fiber reinforced plastic (FRP), polyvinyl fluoride (PVF), polyester, acrylic material, etc. can be used.
[0267] As described above, an active matrix light-emitting device having the light-emitting element of the present invention can be obtained.
[0268] Furthermore, the light-emitting element of the present invention can be used for a passive matrix light-emitting device instead of the above-mentioned active matrix light-emitting device. Figure 5A and 5B A perspective view and a cross-sectional view showing a passive matrix light-emitting device using the light-emitting element of the present invention. Figure 5A is a perspective view of a light emitting device, Figure 5B is along Figure 5A XY line cross-sectional view.
[0269] exist Figure 5A and 5B In the embodiment, an EL layer 504 is provided between a first electrode 502 and a second electrode 503 on a substrate 501. The end of the first electrode 502 is covered by an insulating layer 505. Moreover, a partition layer 506 is provided on the insulating layer 505. The side walls of the partition layer 506 are inclined so that the distance between the two side walls gradually narrows toward the surface of the substrate. In other words, the cross section of the partition layer 506 along the narrow side direction is a trapezoid, and the length of the bottom side (the side in contact with the insulating layer 505, which is one of a pair of parallel sides of the trapezoidal cross section) is less than the length of the top side (the side not in contact with the insulating layer 505, which is the other side of a pair of parallel sides). This type of partition layer 506 can prevent defects in the light-emitting element due to static charge and the like.
[0270] Therefore, a passive matrix light-emitting device including the light-emitting element of the present invention can be manufactured.
[0271] It should be noted that any light-emitting device (active-matrix light-emitting device and passive-matrix light-emitting device) described in Embodiment 4 is formed using the light-emitting element of the present invention and has high light-emitting efficiency, so a light-emitting device with low power consumption can be obtained.
[0272] Note that in Embodiment Mode 4, an appropriate combination of the structures described in Embodiment Modes 1 to 3 can be used.
[0273] (Implementation method 5)
[0274] In the embodiment mode, an electronic device including the light-emitting device of the present invention described in embodiment mode 4 is described. Examples of electronic devices include: cameras such as video cameras and digital cameras; eyeglass displays, navigation systems, sound playback devices (such as car audio stereo systems or audio stereo devices), computers, game consoles, portable information terminals (such as mobile computers, mobile phones, portable game consoles, e-book readers, etc.), image reproducing devices equipped with recording media (specifically, devices capable of reproducing recording media such as digital versatile disks (DVDs) and equipped with a display device capable of displaying images), etc. Specific examples of these electronic devices are shown in FIG. Figures 6A-6D middle.
[0275] Fig. 6A A television receiver according to one embodiment of the present invention is shown, which includes a housing 611, a support base 612, a display portion 613, a speaker portion 614, a video input terminal 615, etc. In the television receiver, the light emitting device of the present invention can be applied to the display portion 613. Since the light emitting element of the present invention has a feature of high emission efficiency, a television receiver with low power consumption can be obtained by using the light emitting device of the present invention.
[0276] Figure 6B A computer according to an embodiment of the present invention is shown, which includes a main body 621, a housing 622, a display portion 623, a keyboard 624, an external connection port 625, a pointing device 626, etc. In the computer, the light emitting device of the present invention can be applied to the display portion 623. Since the light emitting element of the present invention has a feature of high emission efficiency, a computer with low power consumption can be obtained by using the light emitting device of the present invention.
[0277] Figure 6C A mobile phone showing one embodiment of the present invention includes a main body 631, a housing 632, a display portion 633, a sound input portion 634, a sound output portion 635, an operation key 636, an external connection port 637, an antenna 638, etc. In the mobile phone, the light emitting device of the present invention can be applied to the display portion 633. Since the light emitting element of the present invention has a feature of high emission efficiency, a mobile phone with low power consumption can be obtained by using the light emitting device of the present invention.
[0278] Fig.6D A video camera according to the present embodiment is shown, which includes a main body 641, a display portion 642, a housing 643, an external connection port 644, a remote control receiving portion 645, an image receiving portion 646, a battery 647, a sound input portion 648, an operation key 649, an eyepiece portion 650, etc. In this video camera, the light emitting device of the present invention can be applied to the display portion 642. Since the light emitting element of the present invention has a feature of high emission efficiency, a video camera with low power consumption can be obtained by using the light emitting device of the present invention.
[0279] As described above, the light emitting device of the present invention has a wide range of applications, and the light emitting device can be applied to various electronic device fields. By using the light emitting device of the present invention, an electronic device with reduced power consumption can be obtained.
[0280] Furthermore, the light emitting device of the present invention can be used as a lighting device. Figure 7 An example of a liquid crystal display device in which the light emitting device of the present invention is used as a backlight is shown. Figure 7 The liquid crystal display device shown in FIG. 7 includes a housing 701, a liquid crystal layer 702, a backlight 703, and a housing 704. The liquid crystal layer 702 is connected to a driver IC 505. The light emitting device of the present invention serves as the backlight 703, and current is supplied through a terminal 706.
[0281] By using the light emitting device of the present invention as the backlight of the above-mentioned liquid crystal display, a backlight with low power consumption can be obtained. In addition, since the light emitting device of the present invention is a surface light emitting device, a large area can be formed, and a backlight with a large area can also be obtained. Therefore, a large-area liquid crystal display with low power consumption can be obtained.
[0282] Figure 8 This is an example of a desk lamp using the light emitting device of the present invention as a lighting device. Figure 8 The desk lamp shown in FIG. 8 includes a housing 801 and a light source 802, and the light emitting device of the present invention is used as the light source 802. The light emitting device of the present invention has a light emitting element with high emission efficiency, so the light emitting device can be used as a desk lamp with low power consumption.
[0283] Fig. 9 An example of applying the light emitting device of the present invention as an interior lighting system 901 is shown. Since the light emitting device of the present invention can be enlarged, the light emitting device can be used as a large area lighting device. In addition, the light emitting device of the present invention has a light emitting element with high emission efficiency, so the light emitting device can be used as a lighting device with low power consumption. In a room where the light emitting device of the present invention is used as an interior lighting device 901, a Fig. 6A The television receiver 902 of the present invention is shown, where public broadcasts or movies can be enjoyed.
[0284] Note that in Embodiment Mode 5, an appropriate combination of the structures described in Embodiment Modes 1 to 4 can be used.
[0285] (Example 1)
[0286] "Synthesis Example 1"
[0287] In Example 1, a synthesis example of the fluorene derivative represented by the general formula (G1) in Embodiment 1 and in the embodiment of the present invention is described. Specifically, a synthesis method of 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) represented by the structural formula (101) in Embodiment 1 is described. The structure of BPAFLP is shown below.
[0288] [Chemical formula 30]
[0289]
[0290] [Step 1: Synthesis method of 9-(4-bromophenyl)-9-phenylfluorene]
[0291] In a 100 ml three-necked flask, 1.2 g (50 mmol) of magnesium was heated and stirred for 30 minutes under reduced pressure to activate it. After the flask was cooled to room temperature, a few drops of dibromomethane were added under a nitrogen atmosphere to confirm the formation of foam and the generation of heat. After 12 g (50 mmol) of 2-bromobiphenyl dissolved in 10 ml of diethyl ether was slowly added dropwise to the mixture, the mixture was stirred and heated for 2.5 hours under reflux to obtain a Grignard reagent.
[0292] In a 500 ml three-necked flask, 10 g (40 mmol) of 4-bromobenzophenone and 100 ml of diethyl ether were placed, and the previously synthesized Grignard reagent was slowly added dropwise to the mixture, and heated and stirred under reflux for 9 hours.
[0293] After the reaction, the mixture was filtered to obtain a residue. The obtained residue was dissolved in 150 ml of ethyl acetate, 1N hydrochloric acid solution was added thereto until the mixed solution became acidic, and the mixture was stirred for 2 hours. The organic layer of the solution was washed with water. Then magnesium sulfate was added to remove moisture. The suspension was filtered, and the obtained filtrate was concentrated to obtain a candy-like substance.
[0294] Next, the candy-like substance, 50 ml of glacial acetic acid and 1.0 ml of hydrochloric acid were added to a 500 ml recovery flask, and the mixture was added and stirred at 130° C. for 1.5 hours under a nitrogen atmosphere to carry out a reaction.
[0295] After the reaction, the reaction mixture solution was filtered to obtain a residue. The residue was washed with water, sodium hydroxide solution, water and methanol in sequence, and then dried to obtain 11 grams of the target white powder with a yield of 69%. The reaction scheme of the above-mentioned synthesis method is shown in the following (J-1).
[0296] [Chemical formula 31]
[0297]
[0298] [Step 2: Synthesis of 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP)]
[0299] Into a 100 ml three-necked flask were added 3.2 g (8.0 mmol) of 9-(4-bromophenyl)-9-phenylfluorene, 2.0 g (8.0 mmol) of 4-phenyl-diphenylamine, 1.0 g (10 mmol) of sodium tert-butoxide and 23 mg (0.04 mmol) of di(dibenzylideneacetone)palladium(0), and the atmosphere in the flask was replaced with nitrogen. Then, 20 ml of anhydrous xylene was added to the mixture. After the mixture was degassed while being stirred under reduced pressure, 0.2 ml (0.1 mmol) of tri(tert-butyl)phosphine (10 wt% hexane solution) was added to the mixture. The mixture was heated and stirred at 110° C. in a nitrogen atmosphere for 2 hours to react.
[0300] After the reaction, 200 ml of toluene was added to the reaction mixture solution, and the resulting suspension was filtered through Florisil (produced by Wako Pure Chemical Industries, Ltd., catalog number 540-00135) and Celite (produced by Wako Pure Chemical Industries, Ltd., catalog number 531-16855). The obtained filtrate was concentrated and purified by silica gel column chromatography (elution solvent, toluene: hexane = 1: 4). The obtained fraction was concentrated, and acetone and methanol were added thereto. The mixture was irradiated with ultrasonic waves and then recrystallized to obtain 4.1 g of the target white powder with a yield of 92%. The reaction scheme of the above-mentioned synthesis method is shown below (J-2).
[0301] [Chemical formula 32]
[0302]
[0303] The Rf value of the target substance was 0.41, the Rf value of 9-(4-bromophenyl)-9-phenylfluorene was 0.51 and the Rf value of 4-phenyl-diphenylamine was 0.27, and these measured values were measured by silica gel column thin layer chromatography (TLC) (elution solvent, ethyl acetate:hexane=1:10).
[0304] The compound obtained in step 2 above was subjected to nuclear magnetic resonance ( 1 The measured data are shown below. Fig. 10A and 10B show 1 H-NMR spectrum. The measurement results showed that the fluorene derivative BPAFLP (abbreviation) of the present invention represented by the structural formula (101) was obtained.
[0305] 1 H-NMR (CDCl 3, 300MHz): δ (ppm) = 6.63-7.02 (m, 3H), 7.06-7.11 (m, 6H), 7.19-7.45 (m, 18H), 7.53-7.55 (m, 2H), and 7.75 (d, J = 6.9, 2H).
[0306] The following tests were performed on various physical properties of the obtained target substance BPAFLP (abbreviation).
[0307] The absorption spectrum was measured using an ultraviolet-visible spectrophotometer (V-550, manufactured by JASCO Corporation) (measurement range: 200 nm to 800 nm). Fig.11 The absorption spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometers) and the vertical axis represents absorption intensity (arbitrary units). The toluene solution is placed in a quartz cell for measurement, and the displayed spectrum is obtained by subtracting the absorption spectra of quartz and toluene from the absorption spectrum of the sample. For the film, the sample evaporated on the quartz substrate is measured, and the displayed spectrum is obtained by subtracting the absorption spectrum of quartz from the absorption spectrum of the sample. From these spectra, it can be seen that in the case of toluene solution, there is an absorption peak at about 314 nanometers on the long wavelength side, and in the case of the film, there is an absorption peak at about 324 nanometers on the long wavelength side.
[0308] The emission spectrum was measured with a fluorescence spectrophotometer (FS920, manufactured by Hamamatsu Photonics Co., Ltd.). Fig.12 The emission spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometer) and the vertical axis represents absorption intensity (arbitrary unit). The toluene solution is placed in a quartz cell for measurement, and for the film, the sample evaporated on the quartz substrate is measured. From these spectra, the maximum emission wavelength at 386 nanometers can be observed for the toluene solution (excitation wavelength: 330 nanometers), and the maximum emission wavelength at 400 nanometers can be observed for the film (excitation wavelength: 349 nanometers).
[0309] The results of measuring the film with a photoelectron spectrophotometer (AC-2, manufactured by Riken Keiki Co., Ltd.) in this atmosphere showed that the HOMO level of the film was -5.63 eV. The Tauc curve of the film absorption spectrum showed that the absorption edge was 3.34 eV. Therefore, the energy gap in the solid state was about 3.34 eV, which means that the LUMO level of the film was -2.29 eV. This shows that BPAFLP (abbreviation) has a relatively deep HOMO level and a wide band gap (Bg).
[0310] The characteristics of the oxidation-reduction reaction of BPAFLP (abbreviation) were examined using a cyclic voltammetry (CV) curve. Note that the measurement was performed using an electrochemical analyzer (ALS model 600A or 600C, manufactured by BAS Inc.).
[0311] It should be noted that for the measurement of oxidation characteristics, the potential of the working electrode relative to the reference electrode was scanned from -0.10 V to 1.50 V and then from 1.50 V to -0.10 V. It was found that the HOMO level was -5.51 [eV]. In addition, the oxidation peak was still a similar value even after 100 cycles. Accordingly, it was found that the redox repetitive process between the oxidized state and the neutral state has favorable characteristics.
[0312] Note the measurement method described below.
[0313] (Calculate the potential energy of the reference electrode relative to the vacuum level)
[0314] First, the reference electrode (Ag / Ag + Electrode) relative to the potential energy of the vacuum level (eV). In other words, calculate Ag / Ag + The Fermi level of the electrode. It is known that the redox potential of ferrocene in methanol relative to the standard hydrogen electrode is +0.610 [V vs. SHE] (reference: Christian R. Goldsmith et al. J. Am. Chem. Soc., Vol. 124, No. 1, 83-96, 2002). On the other hand, using the reference electrode in Example 1, the redox potential of ferrocene in methanol is calculated to be +0.11 [V vs. Ag / Ag + ]. Therefore, it was found that the potential energy of the reference electrode in Example 1 was 0.50 [eV] lower than the potential energy of the standard hydrogen electrode.
[0315] Note that the potential energy of the standard hydrogen electrode relative to the vacuum level is known to be -4.44 eV (reference: Toshihiro Ohnishi and Tamami Koyama, High molecular EL material, Kyoritsushuppan, pp. 64-67). Accordingly, the potential energy of the reference electrode used in Example 1 relative to the vacuum level is calculated to be -4.44-0.50=-4.94 [eV].
[0316] (CV test conditions of target substances)
[0317] For the solution used for CV measurement, dehydrated dimethylformamide (DMF, product of Sigma-Aldrich Inc., 99.8%, catalog number 22705-6) was used as a solvent, tetra-n-butylammonium perchlorate (n-Bu 4 NClO 4 , Tokyo Chemical Industry Co., Ltd., catalog number T0836) is the supporting electrolyte, dissolved in the solvent so that the concentration of tetra-n-butylammonium perchlorate is 100 mmol / L. In addition, the target to be measured is dissolved in the solvent so that the concentration is 2 mmol / L. A platinum electrode (manufactured by BAS, PTE platinum electrode) is used as the working electrode, a platinum electrode (manufactured by BAS, Pt counter electrode of VC-3, 5 cm) is used as the auxiliary electrode, and an Ag / Ag+ electrode (manufactured by BAS, RE-7 reference electrode, for non-aqueous solvents) is used as the reference electrode. It should be noted that the measurement is performed at room temperature (20°C-25°C). In addition, in all measurements, the scan rate in the CV measurement is set to 0.1 V / s.
[0318] Next, the HOMO levels were calculated from the CV measurements. Fig.13 CV measurement results showing redox characteristics. Fig.13 As shown, the oxidation peak potential (from neutral state to oxidation state) E pa =0.62 V. In addition, the reduction peak potential (oxidized state to neutral state) is 0.52 V. Therefore, the half-wave potential (intermediate potential between Epa and Epc) is calculated, Epa + Epc / 2 [V] is 0.57 V. This shows that the oxidation reaction occurs, and the electrical energy is +0.57 [V vs. Ag / Ag + Herein, as described above, the potential energy of the reference electrode used in Example 1 relative to the vacuum level is -4.94 [eV]; therefore, it should be understood that the HOMO energy level of BPAFLP (abbreviation) is calculated as follows: -4.94-0.57=-5.51 [eV].
[0319] The glass transition temperature was measured by differential scanning calorimetry (Pyris 1DSC, manufactured by Perkin Elmer). According to the measurement results, the glass transition temperature was determined to be 107°C. In this manner, BPAFLP (abbreviation) has a high glass transition temperature and good heat resistance. In addition, there is no crystallization peak; therefore, it was found that BPAFLP (abbreviation) is a substance that is difficult to crystallize.
[0320] (Example 2)
[0321] "Synthesis Example 2"
[0322] In Example 2, a synthesis example of the fluorene derivative represented by the general formula (G1) in Embodiment 1 and in the embodiment of the present invention is described. Specifically, a method for synthesizing 4-phenyl-4′-[4-(9-phenylfluorene-9-yl)phenyl]triphenylamine (abbreviation: BPAFLBi) represented by the structural formula (151) in Embodiment 1 is described. The structure of BPAFLBi is shown below.
[0323] [Chemical formula 33]
[0324]
[0325] [Step 1: Synthesis of 9-(4′-bromo-4-biphenylyl)-9-phenylfluorene]
[0326] In a 500 ml three-necked flask, 5.1 g (22 mmol) of 2-bromobiphenyl was added, and the atmosphere in the flask was replaced with nitrogen. Then, 200 ml of anhydrous tetrahydrofuran (abbreviation: THF) was added to the mixture, and the mixture solution was cooled to -78°C. 14 ml (22 mmol) of a hexane solution of n-butyl lithium was added dropwise to the mixture solution, and the mixture was stirred for 2.5 hours. After that, 6.7 g (20 mmol) of 4-benzoyl-4′-bromobiphenyl was added to the mixture, and the mixture was stirred for 2 hours at -78°C, and then stirred at room temperature for 85 hours.
[0327] After the reaction, 1N dilute hydrochloric acid was added to the reaction solution until the mixed solution was acidic, and the mixture was stirred for 4 hours. The solution was washed with water. After washing, magnesium sulfate was added to remove moisture. The suspension was filtered, and the filtrate obtained was concentrated and purified by silica gel column chromatography (elution solvent, hexane). The fraction obtained was concentrated, and methanol was added thereto, ultrasonic waves were applied, and recrystallization was performed to obtain the target white powder.
[0328] Next, the white powder, 50 ml of glacial acetic acid and 1.0 ml of hydrochloric acid were added to a 200 ml recovery flask, and the mixture was added and stirred at 130°C for 2.5 hours under a nitrogen atmosphere to carry out a reaction.
[0329] After the reaction, the reaction mixture solution was filtered to obtain a filtrate. The filtrate obtained was dissolved in 100 ml of toluene, and washed with water, sodium hydroxide solution and water successively, and magnesium sulfate was added thereto to remove moisture. The suspension was filtered, and the filtrate obtained was concentrated, and acetone and methanol were added thereto. The mixture was irradiated with ultrasonic waves, and then recrystallized to obtain 6.3 grams of target white powder, with a yield of 67%. The reaction scheme of the above-mentioned synthetic method is shown in (J-3) below.
[0330] [Chemical formula 34]
[0331]
[0332] [Step 2: Synthesis method of 4-phenyl-4′-[4-(9-phenylfluoren-9-yl)phenyl]triphenylamine (abbreviation: BPAFLBi)]
[0333] In a 100 ml three-necked flask, 3.8 g (8.0 mmol) of 9-(4′-bromo-4-biphenyl)-9-phenylfluorene, 2.0 g (8.0 mmol) of 4-phenyl-diphenylamine, 1.0 g (10 mmol) of sodium tert-butoxide and 23 mg (0.04 mmol) of di(dibenzylideneacetone)palladium (0) were added, and the atmosphere in the flask was replaced with nitrogen. Then, 20 ml of anhydrous xylene was added to the mixture. After the mixture was degassed while being stirred under reduced pressure, 0.2 ml (0.1 mmol) of tri(tert-butyl)phosphine (10 wt % hexane solution) was added to the mixture. The mixture was heated and stirred at 110° C. for 2 hours in a nitrogen atmosphere to react.
[0334] After the reaction, 200 mL of toluene was added to the reaction mixture solution, and the obtained suspension was filtered through Florisil and Celite. The obtained filtrate was concentrated and purified by silica gel column chromatography (elution solvent, toluene: hexane = 1: 4). The obtained fraction was concentrated, and acetone and methanol were added thereto. The mixture was irradiated with ultrasound and then recrystallized to obtain 4.4 grams of the target white powder with a yield of 86%. The reaction scheme of the above-mentioned synthesis method is shown below (J-4).
[0335] [Chemical formula 35]
[0336]
[0337] The Rf value of the target substance was 0.51, the Rf value of 9-(4′-bromo-4-biphenylyl)-9-phenylfluorene was 0.56 and the Rf value of 4-phenyl-diphenylamine was 0.28, and these measured values were measured by silica gel column thin layer chromatography (TLC) (elution solvent, ethyl acetate:hexane=1:10).
[0338] The compound obtained in step 2 was subjected to nuclear magnetic resonance ( 1 The measured data are shown below. Fig.14A and 14B show 1 H-NMR spectrum. The measurement results showed that the fluorene derivative BPAFLBi (abbreviation) of the present invention represented by the structural formula (151) was obtained.
[0339] 1 H-NMR (CDCl 3, 300MHz): δ (ppm) = 7.04 (t, J = 6.6, 1H), 7.12-7.49 (m, 30H), 7.55-7.58 (m, 2H), and 7.77 (d, J = 7.8, 2H).
[0340] The following tests were performed on various physical properties of the obtained target substance BPAFLBi (abbreviation).
[0341] The absorption spectrum was measured using an ultraviolet-visible spectrophotometer (V-550, manufactured by JASCO Corporation) (measurement range: 200 nm to 800 nm). Fig.15 The absorption spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometers) and the vertical axis represents absorption intensity (arbitrary units). The toluene solution is placed in a quartz cell for measurement, and the displayed spectrum is obtained by subtracting the absorption spectra of quartz and toluene from the absorption spectrum of the sample. For the film, the sample evaporated on the quartz substrate is measured, and the displayed spectrum is obtained by subtracting the absorption spectrum of quartz from the absorption spectrum of the sample. From these spectra, it can be seen that in the case of the toluene solution, there is an absorption peak at about 340 nanometers on the long wavelength side, and in the case of the film, there is an absorption peak at about 341 nanometers on the long wavelength side.
[0342] The emission spectrum was measured with a fluorescence spectrophotometer (FS920, manufactured by Hamamatsu Photonics Co., Ltd.). Fig.16 The emission spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometer) and the vertical axis represents emission intensity (arbitrary unit). The toluene solution is placed in a quartz cell for measurement, and for the film, the sample evaporated on the quartz substrate is measured. From these spectra, the maximum emission wavelength at 386 nanometers can be observed for the toluene solution (excitation wavelength: 345 nanometers), and the maximum emission wavelength at 399 nanometers and 419 nanometers can be observed for the film (excitation wavelength: 348 nanometers).
[0343] The results of measuring the film with a photoelectron spectrophotometer (AC-2, manufactured by Riken Keiki Co., Ltd.) in this atmosphere showed that the HOMO energy level of the film was -5.64 eV. The Tauc curve of the film absorption spectrum showed that the absorption edge was 3.28 eV. Therefore, the energy gap in the solid state is about 3.28 eV, which means that the LUMO energy level of the film is -2.36 eV. This shows that BPAFLBi (abbreviation) has a relatively deep HOMO energy level and a wide band gap (Bg).
[0344] The characteristics of the oxidation-reduction reaction of BPAFLBi (abbreviation) were detected by cyclic voltammetry (CV) curve. It should be noted that an electrochemical analyzer (ALS model 600A or 600C, manufactured by BAS Inc.) was used for measurement. The measurement method is similar to Example 1, so the description of the measurement method is omitted.
[0345] It should be noted that for the measurement of oxidation characteristics, the potential of the working electrode relative to the reference electrode was scanned from -0.10 V to 1.50 V and then from 1.50 V to -0.10 V. It was found that the HOMO level was -5.49 [eV]. In addition, the oxidation peak was still a similar value even after 100 cycles. Accordingly, it was found that the redox repetitive process between the oxidized state and the neutral state has favorable characteristics.
[0346] Fig.17 CV measurement results showing the redox characteristics of BPAFLBi (abbreviation).
[0347] The glass transition temperature was measured by differential scanning calorimetry (Pyris 1DSC, manufactured by Perkin Elmer). According to the measurement results, the glass transition temperature was determined to be 126°C. In this manner, BPAFLBi (abbreviation) has a high glass transition temperature and good heat resistance. In addition, there is no crystallization peak; therefore, it is found that BPAFLBi (abbreviation) is a substance that is difficult to crystallize.
[0348] (Example 3)
[0349] In Example 3, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0350] The element structure of the light emitting element in Example 3 is as follows Fig.18 As shown. The fluorene derivative of the present invention (abbreviation: BPAFLP) is used for the hole transport layer 1512 to form the light-emitting element 2. In addition, the light-emitting element 1 is a comparative light-emitting element formed by using 4,4'-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB) for the hole transport layer 1512. In order to make the light-emitting element 1 and the light-emitting element 2 have the same comparison conditions, the comparative light-emitting element 1 is formed on the same substrate as the light-emitting element 2, and the light-emitting element 1 is compared with the light-emitting element 2. The structural formula of the organic compound in Example 3 is shown below.
[0351] [Chemical formula 36]
[0352]
[0353] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0354] Then, an EL layer 1503 including a plurality of stacked layers is formed on the first electrode 1502. In Embodiment 5, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0355] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Next, on the first electrode 1502, 4,4'-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB) and molybdenum (VI) oxide are co-evaporated to form a first layer 1511 (hole injection layer). The thickness is 50 nm, and the evaporation rate is controlled so that the weight ratio of NPB to molybdenum (VI) oxide is 4:1 = (NPB: molybdenum (VI) oxide). It should be noted that the co-evaporation method is an evaporation method in which multiple materials are evaporated simultaneously by multiple evaporation sources in one processing chamber.
[0356] Next, a hole transport material was deposited on the first layer 1511 by an evaporation method using resistance heating to a thickness of 10 nm to form a second layer 1512 (hole transport layer). Note that comparative light-emitting element 1 was formed using 4,4'-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB), and light-emitting element 2 was formed using 4-phenyl-4'-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP).
[0357] Next, a third layer 1513 (light-emitting layer) is formed on the second layer 1512 by an evaporation method using resistance heating. The third layer 1513 is formed by co-evaporating 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA) to a thickness of 30 nm. The evaporation rate is controlled here so that the weight ratio of CzPA to PCBAPA is 1:0.10=(CzPA:PCBAPA).
[0358] In addition, on the third layer 1513, a film of tris(8-hydroxyquinoline)aluminum(III) (abbreviation: Alq) with a thickness of 10 nanometers is formed by an evaporation method using resistance heating, and a film of bathophenanthroline (abbreviation: BPhen) with a thickness of 20 nanometers is formed thereon, thereby forming a fourth layer 1514 (electron transport layer).
[0359] On the fourth layer 1514, a lithium fluoride (LiF) film is formed to a thickness of 1 nm as a fifth layer 1515 (electron injection layer).
[0360] Finally, an aluminum film was formed to a thickness of 200 nanometers by an evaporation method using resistance heating to form the second electrode 1504. In this way, comparative light-emitting element 1 and light-emitting element 2 were formed.
[0361] It should be noted that except for the second layer 1512, the comparative light-emitting element 1 and the light-emitting element 2 were formed in the same steps.
[0362] The comparative light-emitting element 1 and the light-emitting element 2 thus obtained were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operating characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25° C.).
[0363] Fig.19 The current density and luminance characteristics of Light-Emitting Element 1 and Light-Emitting Element 2 are compared and shown. Fig. 20 The voltage and brightness characteristics of Light-Emitting Element 1 and Light-Emitting Element 2 are shown for comparison. Fig.21 The brightness and current efficiency characteristics of light-emitting element 1 and light-emitting element 2 are compared. Fig.19 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig. 20 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.21 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 1 shows that the comparative light emitting element 1 and the light emitting element 2 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity and current efficiency.
[0364] [Table 1]
[0365] Voltage (V) Chroma x Chromay Current efficiency (cd / A) Comparison of light emitting elements 1 3.8 0.16 0.19 5.2 Light emitting element 2 4.2 0.15 0.21 8.5
[0366] When the driving voltage of light emitting element 2 is 4.2V, the brightness and current value are 880cd / m 2and 0.41mA. By comparing with the comparative light-emitting element 1 using NPB (abbreviation) for the second layer 1512, it is found that the light-emitting element 2 using BPAFLP (abbreviation) for the second layer 1512 has a higher current efficiency. This is because compared with the light-emitting element 1, it is believed that the carrier balance of the light-emitting element 2 is improved. Since the HOMO energy level of BPAFLP (abbreviation) is closer to the HOMO energy level of CzPA (abbreviation) (the main material of the light-emitting layer) than the HOMO energy level of NPB, it is believed that the hole injection property from the hole transport layer to the light-emitting layer is improved. In addition, since the LUMO energy level of BPAFLP (abbreviation) is higher than the LUMO energy level of NPB, it is believed that the electron blocking property from the light-emitting layer to the hole transport layer is improved. In addition, since BPAFLP (abbreviation) has a wide band gap (Bg) (compared with NPB), it is believed that the excitons generated in the third layer (light-emitting layer) 1513 will not be transferred to the adjacent second layer 1512 (that is, there is no quenching) and are restricted.
[0367] (Example 4)
[0368] In Example 4, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0369] The element structure of the light emitting element in Example 4 is as follows Fig.18 The fluorene derivative (abbreviation: BPAFLP) of the present invention was used for the hole transport layer 1512 to form the light emitting element 3. The structural formula of the organic compound in Example 4 is shown below.
[0370] [Chemical formula 37]
[0371]
[0372] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0373] Then, an EL layer 1503 including a plurality of stacked layers is formed on the first electrode 1502. In Embodiment 4, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0374] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Next, 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and molybdenum (VI) oxide were co-evaporated on the first electrode 1502 to form a first layer 1511 (hole injection layer). The thickness was 50 nanometers, and the evaporation rate was controlled so that the weight ratio of CzPA to molybdenum (VI) oxide was 4:1 = (CzPA: molybdenum (VI) oxide).
[0375] Next, a hole transport material was deposited on the first layer 1511 to a thickness of 10 nm by an evaporation method using resistance heating to form a second layer 1512 (hole transport layer). Note that the light-emitting element 3 was formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP).
[0376] Next, a third layer 1513 (light-emitting layer) is formed on the second layer 1512 by an evaporation method using resistance heating. The third layer 1513 is formed by co-evaporating 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA) to a thickness of 30 nm. The evaporation rate is controlled here so that the weight ratio of CzPA to PCBAPA is 1:0.10=(CzPA:PCBAPA).
[0377] Thereafter, a fourth electron transport layer, a fifth electron injection layer, and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. Thus, the light-emitting element 3 was formed.
[0378] The obtained Light-emitting Element 3 was sealed in a glove box of nitrogen atmosphere to prevent contact with air. The operating characteristics of the Light-emitting Element 3 were then measured. Note that the measurement was performed at room temperature (the atmosphere was kept at 25° C.).
[0379] Fig. 22 The current density and brightness characteristics of the light-emitting element 3 are shown. Fig.23 The voltage and brightness characteristics of the light-emitting element 3 are shown. Fig.24 The brightness and current efficiency characteristics of light-emitting element 3 are shown. Fig. 22 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.23 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.24In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 2 shows that the light emitting element 3 has a brightness of 1000 cd / m 2 Nearby voltage, chromaticity and current efficiency.
[0380] [Table 2]
[0381] Voltage (V) Chroma x Chromay Current efficiency (cd / A) Light emitting element 3 3.6 0.16 0.22 6.9
[0382] According to Example 4, it was confirmed that the light-emitting element using the fluorene derivative (abbreviation: BPAFLP) of the present invention has the characteristics and all functions as a light-emitting element. In addition, from the reliability test results, it can be seen that a highly reliable light-emitting element is obtained, in which a short circuit caused by a film defect or the like is not caused even when the light-emitting element continuously emits light.
[0383] Fig.25 The continuous lighting test results of the light emitting element 3 under constant current driving are shown. The initial brightness is set to 1000 cd / m 2 (Assuming 1000cd / m 2 The vertical axis represents relative brightness. Fig.25 As can be seen from the results, Light-emitting Element 3 exhibited 78% of the initial luminance even after 1000 hours, so that Light-emitting Element 3 had a long life. Therefore, it was found that a light-emitting element with a long life can be obtained using the BPAFLP (abbreviation) of the present invention.
[0384] (Example 5)
[0385] In Example 5, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-[4-(9-phenylfluorene-9-yl)phenyl]triphenylamine (abbreviation: BPAFLBi) synthesized in Example 1 and Example 2, a light-emitting element formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) and test results of element characteristics are described.
[0386] The element structure of the light emitting element in Example 5 is as follows Fig.18 The fluorene derivative of the present invention is used for the hole injection layer and the hole transport layer to form a light-emitting element. The structural formula of the organic compound in Example 5 is shown below.
[0387] [Chemical formula 38]
[0388]
[0389] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0390] Then, an EL layer 1503 including a plurality of stacked layers is formed on the first electrode 1502. In Embodiment 5, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0391] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is set downward. The pressure of the vacuum evaporation equipment is reduced to about 10-4Pa. Next, on the first electrode 1502, the fluorene derivative and molybdenum (VI) oxide of the embodiment of the present invention are co-evaporated to form a first layer 1511 (hole injection layer). The thickness is 50 nanometers, and the evaporation rate is controlled so that the weight ratio of the fluorene derivative to the molybdenum (VI) oxide is 4:1 = (fluorene derivative: molybdenum oxide). It should be noted that the light-emitting element 4 is formed using 4-phenyl-4′-[4-(9-phenylfluorene-9-yl)phenyl]triphenylamine (abbreviation: BPAFLBi) as the fluorene derivative, and the light-emitting element 5 is formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) as the fluorene derivative.
[0392] Next, a hole transport material was deposited on the first layer 1511 to a thickness of 10 nm by an evaporation method using resistance heating to form a second layer 1512 (hole transport layer). Note that Light-emitting element 4 was formed using BPAFLBi, and Light-emitting element 5 was formed using BPAFLP.
[0393] Next, a third layer 1513 (light-emitting layer) is formed on the second layer 1512 by an evaporation method using resistance heating. Note that in Example 5, the light-emitting layer has two layers (a first light-emitting layer and a second light-emitting layer). The first light-emitting layer is formed on the second layer 1512 by co-evaporating 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA) to a thickness of 15 nm. The evaporation rate is controlled here so that the weight ratio of CzPA to PCBAPA is 1:0.10=(CzPA:PCBAPA).
[0394] Next, a second light-emitting layer was formed on the first light-emitting layer by resistive heating using an evaporation method. The second light-emitting layer was formed on the first light-emitting layer by co-evaporating 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA) to a thickness of 15 nanometers. The evaporation rate was controlled here so that the weight ratio of CzPA to PCBAPA was 1:0.05 = (CzPA:PCBAPA).
[0395] Thereafter, a fourth electron transport layer, a fifth electron injection layer, and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. In this way, the light-emitting elements 4 and 5 were formed.
[0396] It should be noted that except for the first layer 1511 and the second layer 1512, the light-emitting element 4 and the light-emitting element 5 are formed in the same steps.
[0397] The thus obtained Light-emitting Element 4 and Light-emitting Element 5 were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operating characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25°C).
[0398] Fig.26 The current density and brightness characteristics of Light-Emitting Element 4 and Light-Emitting Element 5 are shown. Fig. 27 The voltage and brightness characteristics of light-emitting element 4 and light-emitting element 5 are shown. Fig.28 The brightness and current efficiency characteristics of light-emitting element 4 and light-emitting element 5 are shown. Fig.26 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig. 27 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.28 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 3 shows that light emitting element 4 and light emitting element 5 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity, current efficiency and external quantum efficiency.
[0399] [Table 3]
[0400]
[0401] According to Example 5, it was confirmed that the light-emitting elements using BPAFLBi (abbreviation) and BPAFLP (abbreviation) respectively have the characteristics and all functions as light-emitting elements. In addition, from the reliability test results, it can be seen that a highly reliable light-emitting element is obtained, in which a short circuit caused by a film defect or the like is not caused even when the light-emitting element continuously emits light.
[0402] Fig.29 The continuous lighting test results showing that light emitting element 4 and light emitting element 5 emit light continuously under constant current drive, with the initial brightness set to 1000 cd / m 2 (Assuming 1000cd / m 2 The vertical axis represents relative brightness. Fig.29 From the results, it can be seen that light-emitting element 4 can show 74% of the initial brightness even after 850 hours, and light-emitting element 5 can show 75% of the initial brightness even after 850 hours, so that light-emitting element 4 and light-emitting element 5 have long life. Therefore, it was found that long-life light-emitting elements can be obtained by using BPAFLBi (abbreviation) and BPAFLP (abbreviation) of the present invention.
[0403] (Example 6)
[0404] In Example 6, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0405] The element structure of the light emitting element in Example 6 is as follows Fig.18 The fluorene derivative of the present invention is used for the hole transport layer to form a light emitting element 6. The structural formula of the organic compound in Example 6 is shown below.
[0406] [Chemical formula 39]
[0407]
[0408] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0409] Then, an EL layer 1503 including a plurality of stacked layers is formed on the first electrode 1502. In Embodiment 6, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0410] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is set downward. The pressure of the vacuum evaporation equipment is reduced to about 10-4Pa. Next, 4,4'-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB) and molybdenum (VI) oxide are co-evaporated on the first electrode 1502 to form a first layer 1511 (hole injection layer). The thickness is 50 nanometers, and the evaporation rate is controlled so that the weight ratio of NPB to molybdenum (VI) oxide is 4:2 = (NPB: molybdenum oxide). It should be noted that the co-evaporation method is an evaporation method in which multiple materials are evaporated simultaneously by multiple evaporation sources in one processing chamber.
[0411] Next, a hole transport material was deposited on the first layer 1511 by an evaporation method using resistance heating to a thickness of 10 nm to form a second layer 1512 (hole transport layer). It should be noted that the light-emitting element 6 was formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP), and the light-emitting element 7 was formed using 4,4′-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB).
[0412] Next, a third layer 1513 (light-emitting layer) is formed on the second layer 1512 by a vapor deposition method using resistance heating. 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II) and acetylacetonate (2-phenylpyridinyl-N,C 2′ )Iridium(III) (Abbreviation: Ir(ppy) 2 acac) to form a 40 nm thick film as the third layer 1513. Here, the evaporation rate is controlled so that CO11II and Ir(ppy) 2 The weight ratio of acac is 1:0.08 = (CO11II:Ir(ppy) 2 acac).
[0413] In addition, on the third layer 1513, a film of di(2-methyl-8-hydroxyquinoline)(4-phenylphenolate)aluminum(III) (abbreviation: BAlq) with a thickness of 10 nanometers is formed by an evaporation method using resistance heating, and a film of bathophenanthroline (abbreviation: BPhen) with a thickness of 20 nanometers is formed thereon, thereby forming a fourth layer 1514 (electron transport layer).
[0414] Thereafter, a fourth electron transport layer, a fifth electron injection layer, and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. In this way, comparative light-emitting elements 6 and 7 were formed.
[0415] It should be noted that except for the second layer 1512, the light-emitting element 6 and the comparative light-emitting element 7 were formed in the same steps.
[0416] The thus obtained light-emitting element 6 and comparative light-emitting element 7 were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operating characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25° C.).
[0417] Fig.30 The current density and luminance characteristics of Light-emitting Element 6 and Comparative Light-emitting Element 7 are shown. Fig.31 The voltage and luminance characteristics of the light-emitting element 6 and the comparative light-emitting element 7 are shown. Fig.32 The luminance and current efficiency characteristics of light-emitting element 6 and comparative light-emitting element 7 are shown. Fig.30 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.31 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.32 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 4 shows that the light emitting element 6 and the comparative light emitting element 7 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity, current efficiency and external quantum efficiency.
[0418] [Table 4]
[0419]
[0420] Fig.33 The emission spectra of Light-emitting Element 6 and Comparative Light-emitting Element 7 are shown.
[0421] like Fig.33As shown, in the comparative light-emitting element 7, in addition to the emission wavelength from the dopant, the emission wavelength from NPB in the hole transport layer is observed. This shows that the ability of NPB to block electrons is low, and even in the NPB of the internal quantum efficiency, some recombination occurs. As a result, it is believed that the current efficiency and the external quantum efficiency are reduced. In addition, it is believed that since NPB has a low triplet excitation energy, the triplet excitation energy is easily transferred from the light-emitting layer to NPB, which leads to a decrease in the current efficiency and the external quantum efficiency. On the other hand, in the light-emitting element 6, only the emission from the dopant in the light-emitting layer is observed, and the emission from BPAFLP (abbreviation) in the hole transport layer is not observed. Accordingly, it is shown that BPAFLP has a high electron blocking ability and also has a large triplet excitation energy. As a result, the excitation energy generated is mainly consumed by the dopant (phosphorescent material in the light-emitting layer) to form light, so that a high current efficiency can be obtained. Therefore, it is confirmed that the BPAFLP (abbreviation) of the embodiment of the present invention can be used for the hole transport layer to obtain an efficient element.
[0422] (Example 7)
[0423] In Example 7, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0424] The element structures of the light-emitting elements 8 to 10 in Example 7 are as follows: Fig.18 As shown. Light-emitting element 9 uses the above-mentioned fluorene derivative of the present invention for forming the transport layer, and light-emitting element 10 uses the above-mentioned fluorene derivative of the present invention for forming the hole injection layer and the hole transport layer. The structural formula of the organic compound in Example 7 is shown below.
[0425] [Chemical formula 40]
[0426]
[0427] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0428] Then, an EL layer 1503 including a plurality of layers stacked is formed on the first electrode 1502. In Embodiment 7, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0429] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Then, on the first electrode 1502, a hole injection material was deposited to a thickness of 50 nanometers to form a first layer 1511 (hole injection layer). It should be noted that when forming the light-emitting element 8 and the light-emitting element 9, 4,4'-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB) and molybdenum (VI) oxide were co-evaporated to form the first layer 1511 (hole injection layer 1511). The thickness was 50 nanometers, and the evaporation rate was controlled so that the weight ratio of NPB to molybdenum (VI) oxide was 4:2=(NPB:molybdenum oxide). In addition, when forming the light-emitting element 10, 4-phenyl-4'-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) and molybdenum (VI) oxide were co-evaporated to form the first layer 1511 (hole injection layer). The thickness was 50 nanometers, and the evaporation rate was controlled so that the weight ratio of BPAFLP to molybdenum (VI) oxide was 4:2=(BPAFLP:molybdenum oxide).
[0430] Next, a hole transport material was deposited on the first layer 1511 by an evaporation method using resistance heating to a thickness of 10 nm to form a second layer 1512 (hole transport layer). It should be noted that the light-emitting element 8 was formed using 4-phenyl-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBA1BP)], and the light-emitting element 9 and the light-emitting element 10 were formed using 4-phenyl-4′-(9-phenylfluorene-3-yl)triphenylamine (abbreviation: BPAFLP).
[0431] Next, a third layer 1513 (light-emitting layer) was formed on the second layer 1512 by an evaporation method using resistance heating. 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II), 4-phenyl-4′-(9-phenyl-9H-carbazyl-3-yl)triphenylamine (abbreviation: PCBA1BP)] and di{2-(4-fluorophenyl)-3,5-dimethylpyridinecarboxylate}(picolinate)iridium(III) (abbreviation: Ir(dmFppr)) were co-evaporated. 2 pic) to form a 40 nm thick film as the third layer 1513. Here, the evaporation rate is controlled so that CO11II is combined with PCBA1BP and Ir(dmFppr) 2 pic) is 1:0.15:0.1 = (CO11II:PCBA1BP:Ir(dmFppr) 2 pic)).
[0432] Thereafter, a fourth electron transport layer, a fifth electron injection layer, and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. In this way, light-emitting elements 8 to 10 were formed.
[0433] It should be noted that light-emitting element 8 to light-emitting element 10 are formed in the same steps except for the first layer 1511 and the second layer 1512.
[0434] The thus obtained Light-emitting Element 8 to Light-emitting Element 10 were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operational characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25° C.).
[0435] Fig.34 The current density and brightness characteristics of light-emitting elements 8 to 10 are shown. Fig.35 The voltage and brightness characteristics of light-emitting elements 8 to 10 are shown. Fig.36 The brightness and current density characteristics of light-emitting elements 8 to 10 are shown. Fig.34 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.35 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.36 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 5 shows that light emitting element 8 to light emitting element 10 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity, current efficiency and external quantum efficiency.
[0436] [Table 5]
[0437]
[0438] Each of the light-emitting elements 8 to 10 can obtain high light emission efficiency; however, it is found that the light-emitting element 9 using BPAFLP for the hole transport layer has a higher current efficiency than the light-emitting element 8. In addition, it is found that the light-emitting element 10 using BPAFLP for both the hole injection layer and the hole transport layer has a higher current efficiency than the light-emitting element 9.
[0439] Fig.37 The continuous lighting test results showing that light emitting elements 8 to 10 continuously emit light under constant current drive, with the initial brightness set to 1000 cd / m 2 (Assuming 1000cd / m 2 The vertical axis represents relative brightness. Fig.37The results show that light emitting element 8 can show 64% of the initial brightness even after 650 hours. Light emitting element 9 can show 71% of the initial brightness after 500 hours, and light emitting element 10 can show 72% of the initial brightness after 500 hours. Therefore, it was found that a long-life light emitting element can be obtained using BPAFLP (abbreviation) according to an embodiment of the present invention.
[0440] (Example 8)
[0441] Here, simulation results are shown indicating that the fluorene derivative according to the embodiment of the present invention is suitable for use as a hole transport material.
[0442] The structural formula used in the simulation is shown below.
[0443] [Chemical formula 41]
[0444]
[0445] First, density functional theory was used to calculate the most stable structures of formula (101) (abbreviation: BPAFLP), formula (109), formula (114), formula (151) (abbreviation: BPAFLBi), formula (164) and NPB in singlet and triplet states. Gaussian 03 was used as a quantum chemical calculation program. 6-311G (d, p) was used as a basis function for H, C and N atoms. B3LYP was used as a functional.
[0446] Next, using the most stable structures in the singlet and triplet states obtained by the above calculations, the excitation energies of the structural formula (101) (abbreviation: BPAFLP), structural formula (109), structural formula (114), structural formula (151) (abbreviation: BPAFLBi), structural formula (164), and NPB were calculated by time-dependent density functional theory. The basis functions and functionals used in the calculations are the same as those in the above calculations.
[0447] Table 6 shows the energy level results of the highest occupied molecular orbital (HOMO) energy level of the most stable structure in the singlet state through the above calculation.
[0448] [Table 6]
[0449]
[0450] From the results in Table 6, it can be seen that the HOMO energy level of the above fluorene derivatives is lower than that of NPB. Therefore, it is confirmed that when any of the above fluorene derivatives is used as a hole transport material, the fluorene derivative has a good property of injecting holes into a light-emitting layer having a deeper HOMO energy level than NPB.
[0451] Table 7 shows the first excitation energy (singlet) results of the most stable structure in the singlet state calculated using TDDFT.
[0452] [Table 7]
[0453]
[0454] As can be seen from Table 7, when any of the above fluorene derivatives is used as a hole transport material, the fluorene derivative has difficulty in releasing singlet excitons on the interface between the light emitting layer and the hole transport layer to the hole transport layer side compared to NPB.
[0455] Table 8 shows the first excitation energy (triplet) of the most stable structure in the triplet state calculated using TDDFT.
[0456] [Table 8]
[0457]
[0458]
[0459] As can be seen from Table 8, when any of the above fluorene derivatives is used as a hole transport material, it is difficult for the fluorene derivative to release triplet excitons at the interface between the light-emitting layer and the hole transport layer from the light-emitting layer to the hole transport layer side compared to NPB. In addition, it was found that when any of the fluorene derivatives is used as a phosphorescent host material, the guest material can be easily excited.
[0460] (Example 9)
[0461] In Example 9, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0462] The element structures of the light emitting element 11 in Example 9 and the comparative light emitting element 12 are as follows: Fig.18 The light emitting element 11 is formed by using the fluorene derivative of the present invention for the hole injection layer and the hole transport layer.
[0463] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0464] Then, an EL layer 1503 including a plurality of layers stacked is formed on the first electrode 1502. In Embodiment 9, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0465] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Then, on the first electrode 1502, a hole injection material is deposited to a thickness of 50 nanometers to form a first layer 1511 (hole injection layer). When forming the light-emitting element 11, 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) and molybdenum (VI) oxide are co-evaporated to form the first layer 1511 (hole injection layer 1511). The thickness is 50 nanometers, and the evaporation rate is controlled so that the weight ratio of BPAFLP to molybdenum (VI) oxide is 4:2=(BPAFLP: molybdenum oxide). In addition, when forming the comparative light-emitting element 12, 4,4′,4″-tri(carbazolyl-9-yl)triphenylamine (abbreviation: TCTA) and molybdenum (VI) oxide are co-evaporated to form the first layer 1511 (hole injection layer). The thickness is 50 nanometers, and the evaporation rate is controlled so that the weight ratio of TCTA to molybdenum (VI) oxide is 4:2=(TCTA: molybdenum oxide).
[0466] Next, a hole transport material is deposited on the first layer 1511 to a thickness of 10 nm by an evaporation method using resistance heating to form a second layer 1512 (hole transport layer). It should be noted that the light-emitting element 11 is formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP), and the comparative light-emitting element 12 is formed using 4,4′,4″-tris(carbazolyl-9-yl)triphenylamine (abbreviation: TCTA).
[0467] Next, a third layer 1513 (light-emitting layer) was formed on the second layer 1512 by a vapor deposition method using resistance heating. 9-[4-(4,5-diphenyl-4H-1,2,4-triazol-3-yl)phenyl]-9H-carbazole (abbreviation: CzTAZ1) and picolinic acid di[2-(4′,6′-difluorophenyl) pyridine acid-N,C 2′ ] Iridium (III) (abbreviation: FIrpic) forms a 30 nm thick film as the third layer. The evaporation rate is controlled here so that the weight ratio of CzTAZ1 to FIrpic is 1:0.06=(CzTAZ1:FIrpic).
[0468] In addition, on the third layer 1513, a film of 3-(4-biphenyl)-4-phenyl-5-(4-tert-butylphenyl)-1,2,4-triazole (abbreviation: TAZ01) with a thickness of 10 nanometers is formed by an evaporation method using resistance heating, and a film of bathophenanthroline (abbreviation: BPhen) with a thickness of 20 nanometers is formed thereon, thereby forming a fourth layer 1514 (electron transport layer).
[0469] Thereafter, a fifth electron injection layer and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. In this way, the light-emitting element 11 and the comparative light-emitting element 12 were formed.
[0470] It should be noted that the light-emitting element 11 to the comparative light-emitting element 12 are formed in the same steps except for the first layer 1511 and the second layer 1512.
[0471] The light-emitting element 11 and the comparative light-emitting element 12 thus obtained were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operating characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25° C.).
[0472] Fig.38 The current density and luminance characteristics of the light-emitting element 11 and the comparative light-emitting element 12 are shown. Fig.39 The voltage and brightness characteristics of the light-emitting element 11 and the comparison light-emitting element 12 are shown. Fig.40 The brightness and current efficiency characteristics of the light-emitting element 11 and the comparative light-emitting element 12 are shown. Fig.38 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.39 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.40 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 9 shows that the light emitting element 11 and the comparative light emitting element 12 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity, current efficiency and external quantum efficiency.
[0473] [Table 9]
[0474]
[0475]
[0476] When the driving voltage of the light-emitting element 11 using the fluorene derivative BPAFLP (abbreviation) of the present invention for the first layer 1511 and the second layer 1512 is 5.2 V, the luminance is 910 cd / m 2, the current value is 0.18mA. When the driving voltage of the comparative light-emitting element 12 using TCTA (abbreviation) instead of BPAFLP (abbreviation) is 5.2V, the brightness is 850cd / m2 and the current value is 0.19mA. Therefore, it is confirmed that the light-emitting element 11 using BPAFLP (abbreviation) for the first layer 1511 and the second layer 1512 has a higher current efficiency than the comparative light-emitting element 12. It was found that applying BPAFLP (abbreviation) of an embodiment of the present invention to a hole injection layer and a hole transport layer can obtain an efficient light-emitting element.
[0477] Fig.41 The emission spectra of Light-emitting Element 11 and Comparative Light-emitting Element 12 are shown.
[0478] In both the light-emitting element 11 and the comparative light-emitting element 12, emission spectra from the phosphorescent doping material FIrpic (abbreviation) were observed, and light emission from the adjacent layer of the third layer 1513 was not observed. This indicates that in both elements, carriers are preferably recombined in the third layer 1513, and light can be emitted from a good carrier balance. This indicates that because the light-emitting element 11 shows a higher current efficiency than the comparative light-emitting element 12 at this time, BPAFLP (abbreviation) has a better carrier balance (blocking electrons from the third layer 1513 and obtaining more holes flowing to the third layer 1513), and its triplet excitation energy is also high. At this time, the LUMO energy level of BPAFLP (abbreviation) of the embodiment of the present invention is almost the same as that of TCTA (abbreviation) (-2.30 eV), and the band gap (Bg) of BPAFLP (abbreviation) is narrower than that of TCTA (abbreviation) (3.40 eV); therefore, BPAFLP (abbreviation) of the embodiment of the present invention is a material with a higher hole transport property. Therefore, it is considered that carrier recombination can be efficiently performed in the light-emitting layer, thereby achieving higher efficiency.
[0479] (Example 10)
[0480] In Example 10, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-4′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: BPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0481] The element structure of the light emitting element 13 in Example 10 is as follows Fig.18 The fluorene derivative (abbreviation: BPAFLP) of the present invention was used for the hole injection layer and the hole transport layer to form the light emitting element 13. The structural formula of the organic compound used in Example 10 is shown below.
[0482] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0483] Then, an EL layer 1503 including a plurality of layers stacked is formed on the first electrode 1502. In Embodiment 9, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0484] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Then, on the first electrode 1502, a hole injection material is deposited to a thickness of 50 nanometers to form a first layer 1511 (hole injection layer). When forming the light emitting element 13, 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP) and molybdenum (VI) oxide are co-evaporated to form the first layer 1511 (hole injection layer 1511). The thickness is 50 nanometers, and the evaporation rate is controlled so that the weight ratio of BPAFLP to molybdenum (VI) oxide is 4:2 = (BPAFLP: molybdenum oxide).
[0485] Next, a hole transport material was deposited on the first layer 1511 to a thickness of 10 nm by an evaporation method using resistance heating to form a second layer 1512 (hole transport layer). Note that the light emitting element 13 was formed using 4-phenyl-4′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: BPAFLP).
[0486] Next, a third layer 1513 (light-emitting layer) was formed on the second layer 1512 by an evaporation method using resistance heating. 4-[3-(Benzo[9,10]phenanthrene-2-yl)phenyl]dibenzothiophene (abbreviation: mDBTPTp-II) and tris(2-phenylpyridinium-N,C 2′ )Iridium(III) (Abbreviation: Ir(ppy) 3 ), forming the third layer 1513. Here, the evaporation rate is controlled so that mDBTPTp-II and Ir(ppy) 3 The weight ratio is 1:0.08 = (mDBTPTp-II:Ir(ppy) 3 ).
[0487] In addition, on the third layer 1513, a 10-nm thick mDBTPTp-II film is formed by evaporation using resistance heating, and a 20-nm thick bathophenanthroline (abbreviation: BPhen) film is formed thereon to form a fourth layer 1514 (electron transport layer).
[0488] Thereafter, a fifth electron injection layer and a second electrode were formed in a manner similar to that of the comparative light-emitting element 1. In this way, the light-emitting element 13 was formed.
[0489] The obtained Light-emitting Element 13 was sealed in a glove box of nitrogen atmosphere to prevent contact with air. The operating characteristics of the Light-emitting Element 13 were then measured. Note that the measurement was performed at room temperature (the atmosphere was kept at 25° C.).
[0490] Fig.42 The current density and brightness characteristics of the light-emitting element 13 are shown. Fig.43 The voltage and brightness characteristics of the light emitting element 13 are shown. Fig.44 The brightness and current efficiency characteristics of the light emitting element 13 are shown. Fig.42 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.43 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.44 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2 ). In addition, Table 10 shows that the light emitting element 13 has a brightness of 1000 cd / m 2 Nearby voltage, chromaticity, current efficiency and external quantum efficiency.
[0491] [Table 10]
[0492]
[0493] According to Example 10, it was confirmed that the light-emitting element using the fluorene derivative (abbreviation: BPAFLP) of the present invention has sufficient characteristics to be used as a light-emitting element. In addition, from the reliability test results, it can be seen that a highly reliable light-emitting element is obtained, in which a short circuit caused by a film defect or the like is not caused even when the light-emitting element continuously emits light.
[0494] In addition, the light emitting element 13 was continuously illuminated under constant current driving for continuous lighting test, and the initial brightness was set to 1000 cd / m 2, even after 1900 hours, 86% of the initial brightness was maintained. Therefore, it was found that the light-emitting element 13 had a long life. Therefore, it was confirmed that a light-emitting element with a long life can be obtained by applying BPAFLP (abbreviation) of an embodiment of the present invention to a hole injection layer.
[0495] (Example 11)
[0496] "Synthesis Example 3"
[0497] In Example 11, a synthesis example of the fluorene derivative represented by the general formula (G1) in Embodiment 1 and in the embodiment of the present invention is described. Specifically, a method for synthesizing 4-phenyl-3′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: mBPAFLP) represented by the structural formula (118) in Embodiment 1 is described. The structure of mBPAFLP is shown below.
[0498] [Chemical formula 42]
[0499]
[0500] [Step 1: Synthesis of 9-(3-bromophenyl)-9-phenylfluorene]
[0501] 30 ml of an anhydrous THF solution of 4.2 g (18 mmol) of 2-bromobiphenyl was added to a 200 ml three-necked flask, and the mixture solution was stirred at -78°C. 11 ml (18 mmol) of a hexane solution (1.57 M) of n-BuLi was added dropwise to the mixture solution, and the mixture was stirred for 2.5 hours. Thereafter, 40 ml of an anhydrous THF solution of 3.9 g (15 mmol) of 3-bromobenzophenone was added dropwise to the mixture, and the mixture was stirred for 2 hours and at room temperature for 16 hours.
[0502] After the reaction, 1N dilute hydrochloric acid was added to the mixture solution, and the mixture was stirred for 1 hour. The mixture was washed with water. The obtained organic phase was concentrated to obtain a candy-like substance.
[0503] Next, the candy-like substance, 20 ml of glacial acetic acid and 1.0 ml of hydrochloric acid were added to a 200 ml recovery flask, and the mixture was added and stirred at 130°C for 2 hours under a nitrogen atmosphere to carry out a reaction.
[0504] After the reaction, the reaction mixture solution was added dropwise to 150 ml of ice water, and a caramel-like solid was precipitated. The insoluble components were removed by decantation. The caramel-like solid was dissolved in 100 ml of toluene, a saturated aqueous solution of sodium bicarbonate was added thereto, and the toluene solution was stirred until no more bubbles were generated. The organic layer was washed with water, and silica gel was added to absorb moisture. The filtrate obtained by filtering the mixture was concentrated, and methanol was added thereto. The mixture was assisted by ultrasound, cooled with ice, and the solid produced was filtered again. 4.9 grams of target white powder were obtained, and the yield was 83%. The reaction scheme of the above-mentioned synthetic method is shown below (J-5).
[0505] [Chemical formula 43]
[0506]
[0507] [Step 2: Synthesis of 4-phenyl-3′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: mBPAFLP)]
[0508] Into a 200 ml three-necked flask were added 2.4 g (6.0 mmol) of 9-(3-bromophenyl)-9-phenylfluorene, 1.5 g (6.0 mmol) of 4-phenyl-diphenylamine, 1.0 g (10 mmol) of sodium tert-butoxide and 3.0 mg (0.005 mmol) of di(dibenzylideneacetone)palladium(0), and the atmosphere in the flask was replaced with nitrogen. Then, 25 ml of anhydrous xylene was added to the mixture. After the mixture was degassed while being stirred under reduced pressure, 0.2 ml (0.1 mmol) of tri(tert-butyl)phosphine (10 wt% hexane solution) was added to the mixture. The mixture was heated and stirred at 130° C. in a nitrogen atmosphere for 2.5 hours to react.
[0509] After the reaction, 200 ml of toluene was added to the reaction mixture solution, and the resulting suspension was filtered through Florisil (produced by Wacker Pure Chemical Industries, Ltd., catalog number 540-00135), alumina and Celite (produced by Wacker Pure Chemical Industries, Ltd., catalog number 531-16855). The obtained filtrate was concentrated and purified by silica gel column chromatography (developing solvent, toluene: hexane = 1: 4). The obtained fraction was concentrated, and acetone and methanol were added thereto. The mixture was irradiated with ultrasound and then recrystallized to obtain 3.2 g of the target white powder with a yield of 97%. The reaction scheme of the above-mentioned synthesis method is shown below (J-6).
[0510] [Chemical formula 44]
[0511]
[0512] The Rf value of the target substance was 0.51, the Rf value of 9-(3-bromophenyl)-9-phenylfluorene was 0.62 and the Rf value of 4-phenyl-diphenylamine was 0.39, and these measured values were measured by silica gel column thin layer chromatography (TLC) (developing solvent, ethyl acetate:hexane=1:10).
[0513] The compound obtained in step 2 was subjected to nuclear magnetic resonance ( 1 The measured data are shown below. Fig.45A and 45B show 1 H-NMR spectrum. The measurement results showed that the fluorene derivative mBPAFLP (abbreviation) of the present invention represented by the structural formula (118) was obtained.
[0514] 1 H-NMR (CDCl 3 , 300MHz): δ (ppm) = 6.72 (d, J = 8.4, 1H), 6.92-7.36 (m, 22H), 7.40-7.44 (m, 4H), 7.54-7.57 (m, 2H), and 7.72-7.75 (m, 2H).
[0515] The molecular weight of the compound obtained in step 2 was measured using a GC-MS detector (ITQ1100 ion trap GC / MS system, manufactured by Thermo Fisher). Accordingly, a main peak with a molecular weight of 561.3 (mode: EI+) was measured, confirming that the target mBPAFLP (abbreviation) was obtained.
[0516] The following tests were performed on various physical properties of the obtained target substance mBPAFLP (abbreviation).
[0517] The absorption spectrum was measured using an ultraviolet-visible spectrophotometer (V-550, manufactured by JASCO Corporation) (measurement range: 200 nm to 800 nm). Fig.46 The absorption spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometers) and the vertical axis represents absorption intensity (arbitrary units). The toluene solution is placed in a quartz cell for measurement. The displayed spectrum is obtained by subtracting the absorption spectra of quartz and toluene from the absorption spectrum of the sample. The sample of the thin film evaporated on a quartz substrate is measured, and the displayed spectrum is obtained by subtracting the absorption spectrum of quartz from the absorption spectrum of the sample. It can be seen from these spectra that for the case of toluene solution, there are absorption peaks at about 310 nanometers and 325 nanometers on the long wavelength side, and for the case of the film, there are absorption peaks at about 312 nanometers and 329 nanometers on the long wavelength side.
[0518] The emission spectrum was measured with a fluorescence spectrophotometer (FS920, manufactured by Hamamatsu Photonics Co., Ltd.). Fig.47The emission spectra of toluene solution and film are shown. The horizontal axis represents wavelength (nanometer) and the vertical axis represents emission intensity (arbitrary unit). The toluene solution is placed in a quartz cell for measurement, and for the film, the sample evaporated on the quartz substrate is measured. From these spectra, the maximum emission wavelength at 382 nanometers (excitation wavelength: 340 nanometers) can be observed for the toluene solution, and the maximum emission wavelength at 393 nanometers (excitation wavelength: 343 nanometers) can be observed for the film.
[0519] The results of measuring the film in this atmosphere with a photoelectron spectrophotometer (AC-2, manufactured by Riken Keiki Co., Ltd.) showed that the HOMO level of the film was -5.73 eV. The Tauc curve of the film absorption spectrum showed that the absorption edge was 3.34 eV. Therefore, the energy gap in the solid state was about 3.34 eV, which means that the LUMO level of the film was -2.39 eV. This shows that mBPAFLP (abbreviation) has a relatively deep HOMO level and a wide band gap (Bg).
[0520] The characteristics of the oxidation-reduction reaction of mBPAFLP (abbreviation) were examined using a cyclic voltammetry (CV) curve. Note that the measurement was performed using an electrochemical analyzer (ALS model 600A or 600C, manufactured by BAS Inc.).
[0521] It should be noted that for the measurement of the oxidation reaction characteristics, the potential of the working electrode relative to the reference electrode was scanned from -0.38 V to 0.69 V and then from 0.69 V to 0.38 V. It was found that the HOMO level was -5.53 [eV]. In addition, the oxidation peak was still a similar value even after 100 cycles. Accordingly, it was found that the redox repetitive process between the oxidized state and the neutral state has favorable characteristics.
[0522] The melting point was measured and found to be 211°C-212°C.
[0523] (Example 12)
[0524] In Example 12, a method for manufacturing a light-emitting element formed using the fluorene derivative 4-phenyl-3′-(9-phenylfluoren-9-yl)triphenylamine (abbreviation: mBPAFLP) synthesized in Example 1 and test results of element characteristics are described.
[0525] The element structure of the light emitting element in Example 12 is as follows Fig.18 The light emitting element 14 is formed by using the above-mentioned fluorene derivative (abbreviation: mBPAFLP) of the present invention for the hole injection layer and the hole transport layer.
[0526] First, indium oxide-tin oxide containing silicon oxide is deposited on the substrate 1501 by sputtering to form the first electrode 1502. Note that the thickness of the first electrode 1502 is 110 nanometers and the electrode area is 2 mm×2 mm.
[0527] Then, an EL layer 1503 including a plurality of layers stacked is formed on the first electrode 1502. In Embodiment 9, the EL layer 1503 has a structure in which a first layer 1511 (hole injection layer), a second layer 1512 (hole transport layer), a third layer 1513 (light-emitting layer), a fourth layer 1514 (electron transport layer), and a fifth layer 1515 (electron injection layer) are stacked in this order.
[0528] The substrate provided with the first electrode 1502 is fixed on the substrate fixture of the vacuum evaporation equipment so that the surface provided with the first electrode 1502 is downwardly disposed. The pressure of the vacuum evaporation equipment is reduced to about 10 -4 Pa. Then, on the first electrode 1502, a hole injection material was deposited to a thickness of 50 nanometers to form a first layer 1511 (hole injection layer). When forming the light-emitting element 14, 4-phenyl-3′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: mBPAFLP) and molybdenum (VI) oxide were co-evaporated to form the first layer 1511 (hole injection layer 1511). The thickness was 50 nanometers, and the evaporation rate was controlled so that the weight ratio of mBPAFLP to molybdenum (VI) oxide was 4:2=(mBPAFLP: molybdenum oxide). It should be noted that when forming the comparative light-emitting element 15, 4,4′-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB) and molybdenum (VI) oxide were co-evaporated to form the first layer 1511 (hole injection layer 1511). The thickness was 50 nanometers, and the evaporation rate was controlled so that the weight ratio of NPB to molybdenum (VI) oxide was 4:2=(NPB: molybdenum oxide).
[0529] Next, a hole transport material was deposited on the first layer 1511 by an evaporation method using resistance heating to a thickness of 10 nm to form a second layer 1512 (hole transport layer). It should be noted that the light-emitting element 14 was formed using 4-phenyl-3′-(9-phenylfluorene-9-yl)triphenylamine (abbreviation: mBPAFLP), and the comparative light-emitting element 15 was formed using 4,4′-di[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviation: NPB).
[0530] Next, a third layer 1513 (light-emitting layer) was formed on the second layer 1512 by an evaporation method using resistance heating. By co-evaporating 9-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazole (abbreviation: CzPA) and 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA), a film with a thickness of 30 nm was formed as the third layer 1513. Here, the evaporation rate was controlled so that the weight ratio of CzPA to PCBAPA was 1:0.075=(CzPA:PCBAPA).
[0531] In addition, on the third layer 1513, a film of tris(8-hydroxyquinoline)aluminum(III) (abbreviation: Alq) with a thickness of 10 nanometers is formed by an evaporation method using resistance heating, and a film of bathophenanthroline (abbreviation: BPhen) with a thickness of 20 nanometers is formed thereon, thereby forming a fourth layer 1514 (electron transport layer).
[0532] On the fourth layer 1514, a lithium fluoride (LiF) film is formed to a thickness of 1 nm as a fifth layer 1515 (electron injection layer).
[0533] Finally, a 200-nanometer-thick aluminum film was formed by an evaporation method using resistance heating, thereby forming the second electrode 1504. In this way, the light-emitting element 14 and the comparative light-emitting element 15 were formed.
[0534] It should be noted that the light-emitting element 14 to the comparative light-emitting element 15 are formed in the same steps except for the first layer 1511 and the second layer 1512.
[0535] The thus obtained light-emitting element 14 and comparative light-emitting element 15 were sealed in a glove box of nitrogen atmosphere to prevent contact with air. Then, the operating characteristics thereof were measured. Note that the measurement was performed at room temperature (the atmosphere was maintained at 25° C.).
[0536] Fig.48 The current density and brightness characteristics of the light-emitting element 14 and the comparative light-emitting element 15 are shown. Fig.49 The voltage and brightness characteristics of the light-emitting element 14 and the comparison light-emitting element 15 are shown. Fig.50 The brightness and current efficiency characteristics of the light-emitting element 14 and the comparative light-emitting element 15 are shown. Fig.48 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents the current density (mA / cm 2 ).exist Fig.49 The vertical axis represents brightness (cd / m 2 ), the horizontal axis represents voltage (V). Fig.50 In the figure, the vertical axis represents the current efficiency (cd / A) and the horizontal axis represents the brightness (cd / m 2). In addition, Table 11 shows that the light emitting element 14 and the comparative light emitting element 15 have a brightness of 1000 cd / m 2 Nearby respective voltage, chromaticity and current efficiency.
[0537] [Table 11]
[0538]
[0539] When the driving voltage of the light emitting element 14 is 3.4V, the brightness is 1100cd / m 2 and the current value is 0.72 mA. It is found that the current efficiency of the light-emitting element 14 using mBPAFLP (abbreviation) for the second layer 1512 is higher than that of the comparative light-emitting element 15 using NPB for the second layer 1512. It should be understood that this is because the carrier balance of the light-emitting element 14 is improved compared with the comparative light-emitting element 15. It is believed that since the HOMO energy level of mBPAFLP (abbreviation) is close to the HOMO energy level of CzPA (abbreviation) (the main material of the light-emitting layer) (compared with NPB), the hole injection property of mBPAFLP from the hole transport layer to the light-emitting layer is improved. In addition, it is believed that since mBPAFLP (abbreviation) has a high LUMO energy level (compared with NPB), the electron blocking property of mBPAFLP (abbreviation) from the light-emitting layer to the hole transport layer is improved. In addition, since mBPAFLP (abbreviation) has a wide band gap (Bg) (compared with NPB), it is believed that the excitons generated in the third layer (light-emitting layer) 1513 will not be transferred to the adjacent second layer 1512 (that is, there is no quenching) and are restricted.
[0540] In addition, when the light emitting element 14 and the comparative light emitting element 15 were continuously illuminated under constant current driving and continuous lighting test was performed, the initial brightness was set to 1000 cd / m 2 (Assuming 1000cd / m 2 =100%, the vertical axis represents relative brightness), after 280 hours, light-emitting element 14 showed 80% of the initial brightness, and comparative light-emitting element 15 showed 72% of the initial brightness, so light-emitting element 14 and comparative light-emitting element 15 have long lifespans. Therefore, it was found that a long-life light-emitting element can be obtained by using the mBPAFLP (abbreviation) of the present invention.
[0541] (Comparative Example 1)
[0542] The synthesis method of 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBAPA) used in Examples 3 to 5 is described in detail.
[0543] [Chemical formula 45]
[0544]
[0545] The synthesis scheme of 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBAPA) is shown in (X-1) below.
[0546] [Chemical formula 46]
[0547]
[0548] 7.8 g (12 mmol) of 9-(4-bromophenyl)-10-phenylanthracene, 4.8 g (12 mmol) of 4-(9-phenyl-9H-carbazole-3-yl)diphenylamine (abbreviation: PCBA), and 5.2 g (52 mmol) of sodium tert-butoxide were added to a 300 ml three-necked flask, and the atmosphere in the flask was replaced with nitrogen. Then, 60 ml of toluene and 0.30 ml of tri(tert-butyl)phosphine (10 wt % hexane solution) were added to the mixture. After degassing the mixture while stirring under reduced pressure, 136 mg (0.24 mmol) of di(dibenzylideneacetone)palladium(0) was added to the mixture. The mixture was stirred at 100° C. for 3 hours. After stirring, about 50 ml of toluene was added to the mixture. The mixture was filtered by suction through production, Celite (produced by Wacker Pure Chemical Industries, Ltd., catalog number 531-16855), alumina and Florisil (produced by Wacker Pure Chemical Industries, Ltd., catalog number 540-00135). The resulting filtrate was concentrated to obtain a yellow solid. The solid was recrystallized from toluene / hexane to obtain 6.6 grams of light yellow powdery solid PCBAPA, which is the target product of the synthesis, with a yield of 75%.
[0549] Then, 3.0 g of the obtained light yellow powdered solid was sublimated and purified by a multi-stage sublimation method. For the sublimation purification conditions, PCBAPA was heated at 350° C. under a pressure of 8.7 Pa and an argon gas flow rate of 3.0 mL / min. After sublimation purification, 2.7 g of light yellow PCBAPA solid was obtained with a yield of 90%.
[0550] The obtained compound was subjected to nuclear magnetic resonance (NMR) measurement. The measurement data are shown below.
[0551] 1 H-NMR (CDCl 3 , 300MHz): δ (ppm) = 7.09-7.14 (m, 1H), 7.28-7.72 (m, 33H), 7.88 (d, J = 8.4Hz, 2H), 8.19 (d, J = 7.2Hz, 1H), and 8.37 (d, J = 1.5Hz, 1H).
[0552] The measurement results showed that 4-(10-phenyl-9-anthracenyl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA) was obtained.
[0553] The light-emitting elements 1 to 5 described in the above embodiments can be formed using 4-(10-phenyl-9-anthryl)-4′-(9-phenyl-9H-carbazolyl-3-yl)triphenylamine (abbreviation: PCBAPA).
[0554] (Comparative Example 2)
[0555] The synthesis method of 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II) used in Examples 6 and 7 is described in detail.
[0556] [Chemical formula 47]
[0557]
[0558] (Y-1) shows a synthesis scheme of 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II).
[0559] [Chemical formula 48]
[0560]
[0561] 2.3 g (6.6 mmol) of 2-(4-iodophenyl)-5-phenyl-1,3,4-oxadiazole, 1.6 g (6.6 mmol) of 3-phenyl-9H-carbazole, and 1.4 g (15 mmol) of sodium tert-butoxide were added to a 100 ml three-necked flask, and the atmosphere in the flask was replaced with nitrogen. 30 ml of toluene and 0.2 ml of a 10 wt% hexane solution of tri(tert-butyl)phosphine were added to the mixture, the pressure of the flask was reduced with an aspirator to degas the mixture, and then the atmosphere in the flask was replaced with nitrogen. 0.058 g (0.10 mmol) of di(dibenzylideneacetone)palladium(0) was added to the mixture, followed by stirring for 15 hours in a nitrogen stream at 80°C. After stirring, toluene was added to the mixture, and the suspension was washed with a saturated aqueous solution of sodium carbonate and saturated brine in sequence. Then, magnesium sulfate was added to the organic layer to remove moisture. Thereafter, the mixture was suction filtered to obtain a filtrate. The obtained filtrate was filtered with Celite (produced by Wacker Pure Chemical Industries, Ltd., catalog number 531-16855) to obtain a filtrate. The compound obtained by concentrating the obtained filtrate was purified by silica gel column chromatography. Toluene was first used as an eluting solvent, and then a mixed solvent of toluene: ethyl acetate = 4:1 was used as an eluting solvent for column chromatography. Acetone was added to the solid obtained by concentrating the obtained fraction and washed with ultrasonic irradiation. The compound was filtered to collect the solid. The collected solid was recrystallized with a mixed solvent of chloroform and hexane to obtain 2.0 grams of a powdery white solid with a yield of 64%.
[0562] 1.1 g of the obtained light yellow powdery solid was sublimated and purified by a multi-stage sublimation method. The sublimation purification was carried out at 240° C. for 16 hours under a reduced pressure of 3.0 Pa and an argon gas flow rate of 5 ml / min. Thus, 0.98 g of a white solid was obtained with a yield of 89%.
[0563] The obtained compound was subjected to nuclear magnetic resonance (NMR) measurement. The measurement data are shown below.
[0564] 1 H-NMR (CDCl 3 , 300MHz): δ (ppm) = 7.30-7.76 (m, 13H), 7.79 (d, J = 8.3Hz, 2H), 8.14-8.24 (m, 3H), 8.35 (sd, J = 1.5Hz, 1H), and 8.39 (d, J = 8.8Hz, 2H).
[0565] The measurement results showed that 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II) was obtained.
[0566] The light-emitting elements 6 to 10 described in the above embodiments can be formed using 3-phenyl-9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11II).
[0567] (Comparative Example 3)
[0568] The synthesis method of 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) used in Example 7 is described in detail.
[0569] [Chemical formula 49]
[0570]
[0571] The synthesis scheme of 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) is shown in (Z-1).
[0572] [Chemical formula 50]
[0573]
[0574] In a 100 ml three-necked flask, 2.0 g (4.9 mmol) of 4-(9-phenyl-9H-carbazole-3-yl)diphenylamine, 1.1 g (4.9 mmol) of 4-bromobiphenyl and 2.0 g (20 mmol) of sodium tert-butoxide were added, and the air in the flask was replaced with nitrogen. Then, 50 ml of toluene and 0.30 ml of tri(tert-butyl)phosphine (10 wt% hexane solution) were added to the mixture.
[0575] After degassing the mixture while stirring under reduced pressure, 0.10 g of di(dibenzylideneacetone)palladium(0) was added to the mixture. The mixture was heated and stirred at 85°C for 5 hours to react. After the reaction, toluene was added to the reaction mixture. The suspension was filtered by Celite (produced by Wacker Pure Chemical Industries, Ltd., catalog number 531-16855), aluminum oxide and Florisil (produced by Wacker Pure Chemical Industries, Ltd., catalog number 540-00135) to obtain a filtrate. The filtrate was washed successively with a saturated aqueous solution of sodium carbonate and saturated brine. Then, magnesium sulfate was added to the organic layer to remove moisture. After drying, the mixture was filtered by suction to remove magnesium sulfate to obtain a filtrate.
[0576] The obtained filtrate was concentrated and purified by silica gel column chromatography. First, a mixed solvent of toluene:hexane = 1:9 was used as an elution solvent, and then a mixed solvent of toluene:hexane = 3:7 was used as another elution solvent for silica gel column chromatography. The solid obtained by concentrating the fraction was recrystallized with a mixed solvent of chloroform and hexane to obtain 2.3 g of white powdery solid with a yield of 84%.
[0577] 1.2 g of the obtained white powdery solid was sublimated and purified by a multi-stage sublimation method. The sublimation purification was carried out at 280° C. for 20 hours under a reduced pressure of 7.0 Pa and an argon gas flow rate of 3 ml / min. Thus, 1.1 g of a white solid was obtained with a yield of 89%.
[0578] The obtained compound was subjected to nuclear magnetic resonance (NMR) measurement. The measurement data are shown below.
[0579] 1 H-NMR (DMSO-d 6 , 300 MHz): δ (ppm) = 7.05-7.20 (m, 7H), 7.28-7.78 (m, 21H), 8.34 (d, J = 7.8 Hz, 1H), and 8.57 (s, 1H).
[0580] The measurement results showed that 4-phenyl-4'-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) was obtained.
[0581] Light-emitting elements 8 to 10 can be formed using 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP).
[0582] (Comparative Example 4)
[0583] Another synthesis method of 4-phenyl-4'-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) used in Comparative Example 3 is described in detail. This synthesis method is preferred because the target substance of higher purity can be easily obtained in high yield.
[0584] [Chemical formula 51]
[0585]
[0586] [Step 1: Synthesis method of 3-(4-bromophenyl)-9-phenyl-9H-carbazole]
[0587] (Z-2) shows a synthesis scheme of 3-(4-bromophenyl)-9-phenyl-9H-carbazole.
[0588] [Chemical formula 52]
[0589]
[0590] In a 300-ml three-necked flask, a mixture of 14 g (50 mmol) of 4-bromoiodobenzene, 14 g (50 mmol) of 9-phenyl-9H-carbazole-3-boric acid, 110 mg (0.5 mmol) of palladium (II) acetate, 300 mg (1.0 mmol) of tri(o-tolyl)phosphine, 50 ml of toluene, 10 ml of ethanol and 25 ml of an aqueous potassium carbonate solution (2 mol / L) was stirred and degassed under reduced pressure, and heated and stirred at 80°C in a nitrogen atmosphere for 6 hours to carry out a reaction.
[0591] After the reaction, 200 ml of toluene was added to the reaction mixture solution, and the resulting suspension was filtered through Florisil (produced by Wacker Pure Chemical Industries, Ltd., catalog number 540-00135) and Celite (produced by Wacker Pure Chemical Industries, Ltd., catalog number 531-16855). The filtrate obtained was washed with water, and magnesium sulfate was added thereto to absorb moisture. The suspension was filtered to obtain a filtrate. The obtained filtrate was concentrated and purified by silica gel column chromatography. At this time, a mixed solvent of toluene and hexane (toluene: hexane = 1:4) was used as an eluting solvent for chromatography. The fraction obtained was concentrated and hexane was added thereto. The mixture was irradiated with ultrasonic waves and then recrystallized to obtain 15 grams of the target white powder with a yield of 75%.
[0592] The Rf value of the target substance was 0.32, and the Rf value of 4-bromoiodobenzene was 0.74, and these measured values were measured by silica gel column thin layer chromatography (TLC) (elution solvent, ethyl acetate:hexane=1:10).
[0593] In addition, the RF value of the by-product 1,4-di(9-phenyl-9H-carbazol-3-yl)benzene was 0.23, (elution solvent, ethyl acetate:hexane=1:10); however, spots were slightly observed on TLC in the reaction suspension.
[0594] As a result, it is understood that since the iodine part in 4-bromoiodobenzene (dihalide and used as source material) has higher reactivity than the bromine part, it selectively (preferably) reacts with the boron compound 9-phenyl-9H-carbazolyl-3-boronic acid (i.e., the dihalide reacts with the boron compound at almost 1:1). In addition, since the RF value of the target substance is sufficiently different from the RF value of the by-product, the target product and the by-product can be easily separated in the above chromatography.
[0595] The compound obtained in step 1 was subjected to nuclear magnetic resonance ( 1 The measured data are shown below.
[0596] 1 H-NMR (CDCl 3 , 300 MHz):δ(ppm)=7.24-7.32(m,1H),7.40-7.64(m,13H),8.17(d,J=7.2,1H),and8.29(s,1H).
[0597] The test results showed that the target substance 3-(4-bromophenyl)-9-phenyl-9H-carbazole was obtained.
[0598] The molecular weight of the above compound was measured using a GC-MS detector (ITQ1100 ion trap GC / MS system, manufactured by ThermoFisher Scientific KK). Accordingly, a main peak with a molecular weight of 397.13 (mode: EI+) was measured, confirming that the target substance 3-(4-bromophenyl)-9-phenyl-9H-carbazole was obtained.
[0599] The GC-MS detector detected a peak of the by-product 1,4-di(9-phenyl-9H-carbazolyl-3-yl)benzene (molecular weight, 560.2). Therefore, it was confirmed that the target substance with high purity can be easily obtained in an extremely high yield through the reaction of step 1.
[0600] [Step 2: Synthesis of 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP)]
[0601] The synthesis scheme of 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) is shown in (Z-3).
[0602] [Chemical formula 53]
[0603]
[0604] 4-Phenyl-diphenylamine and 3-(4-bromophenyl)-9-phenyl-9H-carbazole are reacted in an organic solvent with heating and stirring using a palladium catalyst, a ligand of the palladium catalyst and a base.
[0605] After the reaction, the reaction mixture solution was purified to obtain the target white powder.
[0606] The obtained compound was subjected to nuclear magnetic resonance (NMR) measurement. The measurement results showed that the target substance 4-phenyl-4′-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviation: PCBA1BP) was obtained in Comparative Example 3.
[0607] As described above, it was confirmed that the synthesis method described in Comparative Example 4 can easily obtain the target substance with a relatively high purity in an extremely high yield.
[0608] This application is based on Japanese Patent Application No. 2009-131504 filed with Japan Patent Office on May 29, 2009, the entire contents of which are hereby incorporated by reference.
[0609] Reference numerals
[0610] 101: substrate, 102: first electrode, 103: EL layer, 104: second electrode, 111: layer,
[0611] 112: layer, 113: layer, 114: layer, 115: layer, 301: electrode, 302: electrode, 303: EL layer, 304: EL layer, 305: charge generation layer, 401: source side driving circuit, 402: pixel portion, 403: gate side driving circuit, 404: sealing substrate, 405: sealing agent; 407: spacer, 408: wire, 409: flexible printed circuit (FPC), 410: element substrate, 411: switching TFT, 412: current control TFT, 413: first electrode; 414: insulator, 416: EL layer, 417: second electrode, 418: light-emitting element, 423: n-channel TFT, 424: p-channel TFT, 501: substrate, 502: first electrode, 503: second electrode, 504: EL layer, 505: insulating layer, 506: partition layer, 511: first light-emitting unit, 512: second light-emitting unit, 513: charge generation layer, 521: first electrode, 522: second electrode, 611: housing, 612: supporting substrate, 613: display portion, 614: speaker portion, 615: video audio input terminal, 621: main body, 622: housing, 623: display part, 624: keyboard, 625: external connection part, 626: clicking device, 631: main body, 632: housing, 633: display part, 634: sound input part, 635: sound output part, 636: operation key, 637: external connection part, 638: antenna, 641: main body, 642: display part, 643: housing, 644: external connection part, 645: remote control receiving part, 646: image receiving part, 647: remote control receiving part, 648: remote control receiving part, 649: remote control receiving part, 650: remote control receiving part, 651: remote control receiving part, 652: remote control receiving part, 653: remote control receiving part, 654: remote control receiving part, 655: remote control receiving part, 656: remote control receiving part, 657: remote control receiving part, 658: remote control receiving part, 659: remote control receiving part, 660: remote control receiving part, 661: remote control receiving part, 662: remote control receiving part, 663: remote control receiving part, 664: remote control receiving part, 665: remote control receiving part, 666: remote control receiving part, 667: remote control receiving part, 668: remote control receiving part, 669: remote control receiving part, 670: remote control receiving part, 671: remote control receiving part, 672: remote control receiving part, 673: remote control receiving part, 674: remote control receiving part, 675: remote control receiving part, 676: remote control receiving part, 677: remote control receiving part, 678: remote control receiving part, 679: remote control receiving part, 680: remote control receiving part, 681 7; battery, 648: sound input portion, 649: operation key, 650: eyepiece portion, 701: casing, 702: liquid crystal layer, 703: backlight, 704: casing, 705: driver IC, 706: terminal, 801: casing, 802: light source, 901: lighting device, 902: television receiver, 913: layer, 1501: substrate, 1502: first electrode, 1503: EL layer, 1504: second electrode, 1511: layer, 1512: layer, 1513: layer, 1514: layer, and 1515: layer.
Claims
1. A compound represented by the general formula (G1), wherein Except for the following compounds (253): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents a ring-forming aromatic group having 6 to 13 carbon atoms; Ar 2 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group.
2. A compound represented by the general formula (G1): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents a ring-forming aromatic group having 6 to 13 carbon atoms; Ar 2 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group; When α 3 When the group has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group.
3. A compound represented by the general formula (G1), wherein Except for the following compounds (253): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 2 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group.
4. A compound represented by the general formula (G1): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 2 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group; When α 3 When the group has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group.
5. A compound represented by the general formula (G1): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents a ring-forming aromatic group having 6 to 13 carbon atoms; Ar 2 represents any one of a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group.
6. A compound represented by the general formula (G1): in: R 1 To R 8 Each independently represents a hydrogen atom; α 1 and α 2 each independently represents a substituted or unsubstituted phenylene group; Ar 1 represents any one of a substituted or unsubstituted biphenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 2 represents any one of a substituted or unsubstituted naphthyl group, a substituted or unsubstituted fluorenyl group and a substituted or unsubstituted spirofluorenyl group; Ar 3 represents any one of an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; when the aryl group having 6 to 12 carbon atoms has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group; m and n are independently 0 or 1; J is 0, α 4 is a substituted or unsubstituted phenylene group; k is 1, except for the case of p-phenylene, α 3 is a substituted or unsubstituted phenylene group; When α 3 When the group has a substituent, the substituent is any one of an alkyl group, a phenyl group, a biphenyl group and a naphthyl group.
7. The compound according to any one of claims 1 to 6, wherein Ar 3 Any one of the substituents shown in the following formulas (Ar3-6) to (Ar3-8) 8 . A light-emitting element comprising the compound according to claim 1 .
Citation Information
Patent Citations
Amine compound having fluorene group as framework, process for producing the amine compound, and use of the amine compound
JP2006151935A
Aromatic amine compound and light-emitting element, light-emitting device and electronic device produced by using aromatic amine compound
JP2007284431A
Organic electroluminescence element
JP2008147400A
Benzofluorene compound and use thereof
JP2008201769A
Light-Emitting Element, Light-Emitting Device, and Electronic Appliance
US20090058278A1